Genomic analysis of Escherichia coli, Enterobacter hormaechei, and Cupriavidus gilardii isolated from Cacatua alba - Julia Penna de Andrade; Henrique da Silva Vieira; Camilla Faria Soares; Marcela Laryssa Oliveira Duarte; André Almeida Fernandes; Hannah Luiza Gonsalves Coelho; Victória Veiga Alves; Bertram Brenig; Vasco Ariston de Carvalho Azevedo; Flávia Figueira Aburjaile; Nelson Rodrigo da Silva Martins (Veterinary Research Communications, 2026)
The objective of this study was to perform genomic, phylogenomic, and phenotypic characterization of bacterial isolates from a captive Cacatua alba to investigate their antimicrobial resistance profiles, virulence-associated genes, and genomic relationships with publicly available strains. Bacterial isolates obtained from the lungs and encephalon were identified as Escherichia coli (AV037), Enterobacter hormaechei (AV038), and Cupriavidus gilardii (AV039). Comparative genomic analyses, phylogenomic reconstruction, and antimicrobial susceptibility testing (AST) were performed. Genomic analysis identified multiple antimicrobial resistance-associated genes in AV037, AV038, and AV039, with genes associated with efflux pumps, particularly those in the resistance-nodulation-cell division (RND) family, as the predominant resistance-associated mechanism identified. Most identified genes are intrinsic to the respective bacterial species and do not necessarily confer phenotypic antimicrobial resistance when present alone. Phenotypic testing confirmed multidrug-resistant (MDR) profiles, with resistance to β-lactams and aminoglycosides. Susceptibility to carbapenems was preserved in AV037 and AV038, whereas AV039 exhibited resistance to meropenem. Phylogenomic analysis demonstrated that AV037 and AV038 clustered with strains recovered from diverse hosts and geographic regions. In contrast, AV039 clustered predominantly with environmental and human-associated isolates, including strains harboring the mcr-5 gene. These findings are consistent with previous reports describing the recovery of C. gilardii from both environmental and clinical sources. Overall, this study documents the occurrence of MDR bacteria carrying resistance and virulence-associated determinants in a captive C. alba , highlighting the value of genomic surveillance to improve our understanding of the distribution of clinically relevant bacterial isolates across different ecological settings.

Eucalyptus globulus and Cymbopogon flexuosus essential oils antimicrobial and conservative effects against Salmonella enterica serovar typhimurium and possible cytotoxicity: an in vitro and in situ investigation in inoculated pork sirloin - Cleiton Jesus Andrade Pereira; Vithor Parada Garcia; Vitória Rose de Andrade; Milena Mattes Cerveira; Jéssica Silveira Vitoria; David de Andrade Cabral; Eliezer Avila Gandra; Janice Luehring Giongo; Rodrigo de Almeida Vaucher (Brazilian Journal of Microbiology, 2026)
Foodborne illnesses, particularly those caused by Salmonella spp., represent a major global health concern, with S. typhimurium being a significant contributor to outbreaks. The persistence of S. typhimurium in food production environments and its resistance to conventional disinfectants highlight the need for alternative antimicrobial solutions. Essential oils (EOs) from Eucalyptus globulus (EGEO) and Cymbopogon flexuosus (CFEO) have shown antimicrobial potential against S. typhimurium , but their mechanisms of action and cytotoxic effects on eukaryotic cells require further investigation to assess their safety for food applications, particularly in situ. We evaluated cytotoxicity in erythrocytes and zebrafish liver (ZF-L) cells using hemolysis (HA), MTT, and NR uptake assays. Additionally, we investigated the antimicrobial behavior of EGEO and CFEO against S. typhimurium ATCC 14,028 through MIC/MBC tests, time-kill assays, and a newly designed TSI-adapted test to assess the EOs’ impact on bacterial metabolism. An in situ experiment was also conducted to evaluate the preservative effects of EGEO and CFEO on pork sirloin contaminated with an infectious dose of S. typhimurium and treated with EO-based brines for 7 days under refrigeration. We monitored the presence of Salmonella spp., as well as pH, calcium (Ca²⁺), and magnesium (Mg²⁺) concentrations in the brined samples. Results indicated that CFEO was hemolytic above 0.73 mg/mL and EGEO above 0.45 mg/mL. The MTT assay showed that CFEO did not impair mitochondrial function from 2.941 mg/mL and EGEO from 14.36 mg/mL. NR uptake assay showed that both EOs did not impaired lysossomal function in ZF-L. The MICs and MBCs for CFEO and EGEO were 0.37 mg/mL and 1.79 mg/mL, respectively. Time-kill assays revealed bactericidal effects for CFEO at 4x and 2x MIC within 6 h, while EGEO showed a bactericidal effect only at 4x MIC. The EO-TSI agar assay demonstrated that EGEO inhibited sugar fermentation and sulfur metabolism, while CFEO impacted peptone oxidation and protein metabolism. In situ analyses showed CFEO caused more significant changes in color and odor of the pork samples than EGEO, while both maintained pH levels around 6. Ca²⁺ and Mg²⁺ levels were lower in CFEO-treated samples. Microbiological data confirmed the absence of Salmonella spp. in all samples except for two in the CFEO-brine group. None of the samples showed signs of autolysis or putrefaction, suggesting that both CFEO and EGEO, particularly EGEO, are feasible alternatives as food preservatives, depending on the desired application.

Chemical modifications of diphenyl diselenide enhance its anti-Sporothrix spp. activity and exhibit synergism with itraconazole - Jéssica Estefania Dávila Hidalgo; Melissa Orzechowski Xavier; Mariana Rodrigues Trápaga; Beatriz Cardoso; Mônica Campos dos Santos; Diulien Canary; Gilson Zeni; Cristina Wayne Nogueira; Rodrigo Almeida-Paes; Rosely Maria Zancopé-Oliveira; Vanice Rodrigues Poester (Brazilian Journal of Microbiology, 2026)
Sporotrichosis is a globally distributed subcutaneous mycosis caused by fungi belonging to the Sporothrix genus. The limitations of current treatment options for sporotrichosis have driven an urgent search for new antifungal drugs. Diphenyl diselenide (PhSe)₂, a stable organoselenium, has promising activity against Sporothrix spp. Since chemical modifications in molecules can enhance their antifungal properties, this study aimed to evaluate the anti- Sporothrix activity of two analogs of (PhSe)₂—p-methoxyl-diphenyl diselenide (BMD) and bis-(3-trifluoromethylphenyl) diselenide (CF3)—both alone and in combination with itraconazole (ITZ). A total of 25 Sporothrix spp. isolates ( S. brasiliensis n = 20; S. schenckii n = 4 and S. globosa n = 1) were included. The microdilution and checkerboard assays were used to assess its antifungal activity alone and in combination, respectively. BMD inhibited all isolates, with a total minimum inhibitory concentration ranging from 2 to 16 µg/mL. In contrast, CF3 exhibited only a partial minimum inhibitory concentration activity in 92% of isolates at concentrations ranging from 2 to 16 µg/mL. When combined with ITZ, both compounds predominantly exhibited a synergistic effect (100% for BMD and 73% for CF3). Our study presents pioneering data on two organoselenium compounds with significant in vitro activity against the main pathogenic Sporothrix species, both alone and in combination with ITZ. Further studies are needed to determine whether these in vitro findings translate into in vivo efficacy.

Multilocus sequence typing and genomic characterization of the novel Streptomyces strain SCPE-10, that resists 2,4-D toxicity and has bioremediation potential - Nildo Alfredo Nhampossa; João Victor Castro de Almeida Araújo; Vicente Almeida Serafim da Silva; João Ricardo Vidal Amaral; Cinara Souza da Conceição; Carlos Alberto Xavier Gonçalves; Eamim Daidrê Squizani; Sheila da Silva; Marcia Soares Vidal; Yinglong Chen; Andrew Macrae; Rodrigo Pires do Nascimento (Brazilian Journal of Microbiology, 2026)
The widespread use of aromatic herbicides such as 2,4-dichlorophenoxyacetic acid (2,4-D) has led to persistent environmental contamination, requiring efficient and sustainable biodegradation strategies. In this study, we isolated and characterized a novel actinobacterial strain, Streptomyces sp. SCPE-10, from contaminated coastal soil, capable of using 2,4-D as its sole carbon source. Phenotypic assays revealed robust growth on aromatic substrates, while whole-genome sequencing (Submission no. SUB15461668 ) followed by multilocus sequence analysis (16 S rRNA, recA, rpoB, atpD, gyrB, and trpB) revealed that SCPE-10 is closely related to Streptomyces phaeoluteichromatogenes . Functional genome annotation revealed a high abundance of genes involved in aromatic compound degradation, including cytochrome P450 monooxygenases, ring-cleaving dioxygenases, and dehalogenases. KEGG and antiSMASH analyses identified multiple metabolic pathways and 28 biosynthetic gene clusters (BGCs), including clusters for polyketides, nonribosomal peptides, terpenes, siderophores, and ectoine. Notably, SCPE-10 harbors key genes related to the degradation of benzoate, naphthalene, toluene, xylene, and 2,4-D, indicating broad-spectrum catabolic potential. These findings suggest that Streptomyces sp. SCPE-10 is a promising candidate for the bioremediation of herbicide-contaminated environments and the exploration of novel secondary metabolites.

A new species of Cervellus Szépligeti, 1904 (Hymenoptera, Braconidae, Braconinae) from Brazil and the first record of the genus parasitizing Lepidoptera - Antonielson Bezerra da Silva; Rodrigo Almeida Pinheiro (Zoologischer Anzeiger, 2026)

Biotechnological potential of Plant Growth-Promoting Rhizobacteria from the rhizosphere of native species of the Caatinga biome - Priscila Helena Machado; Luan Rodrigo Gil de Brito; Mariana Martins Ferreira Lourenço; Luiz Victor de Almeida Dantas; Bruno Coutinho Moreira (Physiological and Molecular Plant Pathology, 2026)

Role of kaolinite epigenesis in ferruginous oolitic micronodule formation in Plinthosols from Central Brazil - Daniela Schievano de Campos; Thiago Tavares Vidoca; Raphael Rodrigues Brizzi; Hermes Dias Brito; Michele Ribeiro Ramos; Rodrigo Estevam Munhoz de Almeida; Pablo Vidal-Torrado (CATENA, 2026)

Collaborative monitoring networks refine jaguar habitat suitability and reveal conservation gaps in the Brazilian Cerrado - Lucas Gonçalves da Silva; Marco Aurélio Mendes Elias; Juliana Silveira dos Santos; Anah Tereza de Almeida Jácomo; Douglas Santos; Ennio Painkow Neto; Fabio Hudson Souza Soares; Gabriel Caputo de Carvalho; Giselle Bastos Alves; Gonzalo Barquero; Igor Fagundes Perfeito; Marina Motta de Carvalho; et al. (Biological Conservation, 2026)

First report of Angiostrongylus vasorum parasitizing lesser grison (Galictis cuja) (Mustelidae) in Brazil - Julia Somavilla Lignon; Maiza Paixão Souza; Natália Büttenbender; Pedro Almeida Rezende; Raqueli Teresinha França; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Felipe Geraldo Pappen; Diego Moscarelli Pinto (Veterinary Research Communications, 2026)
Angiostrongylus vasorum is a metastrongylid nematode that parasitizes the pulmonary arteries and right heart of canids, being the etiological agent of canine angiostrongylosis, a disease of growing veterinary concern due to its expanding geographic distribution and the involvement of domestic and wild hosts. In Brazil, the parasite has been reported mainly in domestic dogs and some wild canids, and its occurrence in mustelids has been documented only once previously. This study reports the first occurrence of A. vasorum infecting a lesser grison ( Galictis cuja ) in Brazil. The mustelid was found after being accidentally run over by a vehicle on a highway in the south of the country. Clinical, physical, and complementary examinations were performed for clinical screening. In the parasitological examination of feces, nematode larvae were recovered and identified morphometrically and molecularly through conventional PCR targeting to the COX1 gene, followed by sequencing and phylogenetic analysis. The results confirmed the presence of A. vasorum , showing 99–100% identity with sequences of the same species deposited in GenBank. Therefore, we document here the first report of A. vasorum parasitizing G. cuja . Thus, the number of known host species parasitized by this helminth is expanded. Furthermore, we provide a new molecular sequence, contributing to the knowledge of this nematode in South America.

Experimental simulations and regional estimates of mercury emissions from fire-affected Cerrado soils (Central Brazil) - Lucas Cabrera Monteiro; Jeremie Garnier; Ronaldo de Almeida; Wanderley Rodrigues Bastos; Cleber Lopes Filomeno; Rodrigo Nunes de Souza; Uidemar Morais Barral; Fermin Fidel Herrera Aragón; Tharcianny Krisllen Nascimento da Silva Oliveira; Jurandir Rodrigues de Souza; José Vicente Elias Bernardi (Applied Geochemistry, 2026)

Fruit Quality of Passiflora Cincinnata at Different Ripening Stages Under Irrigated and Rainfed Cultivation - Giuliana Naiara Barros Sales; Marília Hortência Batista Silva Rodrigues; Toshik Iarley da Silva; Rodolfo Rodrigo de Almeida Lacerda; Josélio dos Santos da Silva; Daniel da Conceição Almeida; Ana Clara Farias Siqueira; Walter Esfrain Pereira; Pahlevi Augusto de Souza; Genilson Lima Diniz; Saint Clair Lira Santos; Geovani Soares de Lima; et al. (Applied Fruit Science, 2026)

Seed desiccation tolerance and conservation of sapucaia, an emerging functional Brazil nut tree from the Atlantic and Amazon forest biomes - Caroline Palacio de Araujo; Ingridh Medeiros Simões; Joana Silva Costa; Taísa de Fátima Rodrigues de Almeida; Débora Pellanda Fagundes; Eduardo Santos Cade; Emanuel Bizareli de Moraes; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; José Eduardo Macedo Pezzopane; José Carlos Lopes; Heloisa Oliveira dos Santos; et al. (Journal of Stored Products Research, 2026)

Bloom of Blixaea quinquecornis (Abé) Gottschling (Dinophyceae) with Chaetoceros tenuissimus Meunier in the South Atlantic: Morphology, molecular characterization, and toxins - Marcella Guennes; Amanda Santos Goulart; Fabiano Salgueiro; Priscila Kienteca Lange; Rodrigo Barcellos Hoff; Luana Souza Futigami; Rodrigo Almeida Ferreira da Silva; Andréa Shirley Xavier da Silva; Pedro Augusto Mendes de Castro Melo; Mauro de Melo Júnior; Silvia Mattos Nascimento (Journal of Environmental Sciences, 2026)

Large-scale toxic bloom of Dinophysis acuminata complex following a major flood disaster in southern Brazil - Luiz L. Mafra; Bruna Fernanda Sobrinho; Ana Martínez; Karoline Magalhães F. Lubiana; Regiane Valejo Maciel; José Guilherme F. Bersano; Luciano F. Fernandes; Fabiola Kaviatkovski; Pedro Almeida Rodrigo; Rafaela Cristine Zem; Carlos E.J.de Azevedo Tibiriçá; Mathias Alberto Schramm; et al. (Harmful Algae, 2026)

Early weaning in pregnant cows as a fetal programming strategy alters the muscle metabotype and carcass traits in Nelore cattle - Matheus Sousa de Paula Carlis; Gabriela Abitante; Thiago Kan Nishimura; Carl Robertson Dahlen; Nara Regina Brandão Cônsolo; Luiz Alberto Colnago; Fernanda Maria Marins Ocampos; Germán Darío Ramírez-Zamudio; Patricia Maloso Ramos; Saulo Luz Silva; Miguel Henrique de Almeida Santana; Arlindo Saran Netto; et al. (Tropical Animal Health and Production, 2026)
This study evaluated early weaning (EW) versus conventional weaning (CW) and dam parity (DP) effects on carcass traits, meat quality, and the muscle metabolome of male offspring exposed in utero during the intervention. A randomized complete-block design with a 2 × 2 factorial arrangement compared weaning strategies (WS: EW at 150 d lactation/80 d gestation vs. CW at 240 d lactation/170 d gestation) and dam parities (DP: multiparous [MP] vs. secundiparous [SP]). Carcass and meat quality data were analyzed considering the dams as experimental unit by using the Mixed procedure, considering the WS and DP as fixed effect, and their interaction. There was interaction between WS×DP ( P < 0.01) for hindquarter fat trim where EW-MP and CW-MP carcasses required more trim fat than EW-SP. EW bulls tended to reduce drip loss ( P = 0.07), tended to increased pistola hindquarter (% of carcass; P = 0.09), while significantly raising ultimate carcass pH ( P = 0.04) versus CW. An untarget 1 H NMR-based metabolomic approach was applied to detect metabolic changes. Pathway analysis of differentially abundant metabolites revealed the upregulation of betaine and glycerolipid metabolism, methylhistidine metabolism for WS and homocysteine degradation, phosphatidylethanolamine synthesis and selenoamino acid metabolism for DP. Offspring of MP dams had heavier cold carcasses ( P = 0.03), greater Forequarter, brisket, shank ( P < 0.03), smaller pistola hindquarter and top sirloin cap ( P ≤ 0.05) than those of SP. These results indicate that WS and DP induce metabolomic shifts favoring muscular hypertrophy and one-carbon metabolism, which may enhance muscularity without impairing meat quality.

Beyond milk yield: could resilience be revealed as deviations through the first lactation curve in Holstein cows? - Rafaela Martins; Altair Antônio Valloto; Roberto Carvalheiro; Lucia Galvão de Albuquerque; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2026)

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Addressing imbalanced data and feature engineering for abnormal water consumption detection with machine learning models - Mahelvson Bazilio Chaves; Fábio Rodrigo de Lima e Silva; Adiel Teixeira de Almeida Filho (Utilities Policy, 2026)

Regional patterns of environmental variability in mangrove ecosystems along the southeastern Brazilian coast - Marcelo Antonio Amaro Pinheiro; Luis Felipe de Almeida Duarte; Caio Rodrigues Nobre; Esli Emanoel Domingues Mosna; Rodrigo dos Santos Rodriguez-Lopes; Todor Petkov; Aleksandar Dimitrov; Dimitrinka Ivanova (Regional Studies in Marine Science, 2026)

Prolonged In Vitro Exposure to Methylmalonic Acid Induces Inflammation, Glutamate Metabolism Disruption, and Alters Functional Gene Expression in C6 Astroglial Cells - Rômulo Rodrigo de Souza Almeida; Larissa Daniele Bobermin; Izaviany Schmitz; Filipe Renato Pereira Dias; Caio César Ramalho Bezerra; Mariana Rocke-Peters; Ester Rezena; Krista Minéia Wartchow; Fernanda Urruth Fontella; Diogo Onofre Souza; Moacir Wajner; Carlos-Alberto Gonçalves; et al. (Neurotoxicity Research, 2026)
Methylmalonic acidemia is an inherited neurometabolic disorder characterized by accumulation of methylmalonic acid (MMA) in different tissues, particularly in the brain. As a result, patients frequently exhibit progressive neurological deterioration, accompanied by episodes of acute encephalopathy following metabolic decompensation. Astrocytes are glial cells that maintain the central nervous system homeostasis and may be important cellular targets of MMA-induced dysfunction. However, most in vitro experimental models for the study of methylmalonic acidemia are based on short-term exposure to the toxic metabolites that accumulate in patients. In this study, we used a prolonged experimental model, which has not been yet explored in the context of glial cells, focusing on the inflammatory response, glutamate metabolism, and putative signaling pathways that can contribute to understanding cellular damage observed in methylmalonic acidemia. It is emphasized that MMA is persistently elevated in the brain of the affected patients. Prolonged MMA exposure induced inflammation with significant increase in gene expression of cyclooxygenase 2, interleukin (IL)-1β and its receptor (IL1R1), and IL-6, accompanied by a decrease in IL-10 expression. MMA also increased glutamate uptake and the activity and gene expression of the enzyme glutamine synthetase, while it downregulated glial cell-derived neurotrophic factor (GDNF). The expression of NFκB, p38 MAPK, Nrf2, heme oxygenase 1, PGC-1α, and sirtuin 1 were also modulated by MMA treatment, indicating the critical role of these signaling pathways in the MMA-induced persistent gliotoxicity. Finally, it is conceivable that these changes may significantly contribute to clarify the pathogenesis of methylmalonic acidemia.

Meta-analysis of woody plant diversity and aboveground biomass stock co-benefits across Amazon agroforestry systems - Thamires Campos de Almeida; Silvio Nolasco de Oliveira Neto; Arthur da Cruz Silva; Rodrigo Gomes Gorsani; Lorena Evangelista Fernandes; Sebastião Venâncio Martins; Mehdi Heydari; Andrés Iván Prato; Lisandra Mendes Louzada-Camilo; Ana Luiza Rangel; Jamerson Souza da Costa; Alisson Lopes Rodrigues; et al. (Agroforestry Systems, 2026)

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Patterns of resource use in loggerhead turtle (Caretta caretta) from the Southwestern Atlantic Ocean - Celina Carolina Almeida; Rodrigo F. Bastos; Sérgio C. Estima; Andrine Paiva da Silva; Gabriela M. Vélez-Rubio; Danielle S. Monteiro (Marine Biology, 2026)
The Southwestern Atlantic Ocean (SWAO) is an important feeding and developmental area for loggerhead turtle ( Caretta caretta ). However, long-term patterns of resource use across life stages and sexes remain poorly understood for the species in this region. Here, we used stable isotope analysis (SIA) of sequential layers of carapace scutes to investigate resource use of loggerhead turtles in the SWAO across life stages and sexes. Scute samples were collected from 42 individuals stranded or incidentally caught by pelagic longline and bottom pair trawl fishery in southern Brazil and Uruguay (from 31º21′S–51º05′W to 34º55′S–56º09′W), between 2013 and 2024. Cluster analysis based on δ¹⁵N values revealed two distinct groups, corresponding to oceanic and neritic foraging habitats, whereas linear mixed models indicated ontogenetic increases in δ¹³C and δ¹⁵N values consistent with habitat shifts. Significant differences between sexes were observed only for δ¹³C values. Bayesian mixing models (MixSIAR) were used to estimate prey contributions to the diet, based on isotopic values from the literature, revealing a dominance of pelagic prey in oceanic non-shifters and of benthic invertebrates in neritic non-shifters. Shifters showed a transition from oceanic to neritic habitats, with a dietary shift from pelagic to benthic prey, reflecting two main ontogenetic shift patterns: discrete and facultative. Our results enhance the understanding of life-history variation in loggerhead turtles and highlight that sequential analysis of carapace scutes is a valuable tool for reconstructing long-term resource use patterns, providing a broader view of the ecology of this long-lived and endangered species.

Curcumin versus placebo in benign prostatic hyperplasia: a systematic review and meta-analysis - Diogo Souto Santana; Breno Cordeiro Porto; Rafael Baldissera Cardoso; Guilherme Melchior Maia Lopes; Luiz Guilherme Serrão Gimenez; Carlo Camargo Passerotti; Ronaldo Maia; Fernando Gonçalves Almeida; Rodrigo Afonso da Silva Sardenberg; José Arnaldo Shiomi da Cruz (European Journal of Clinical Pharmacology, 2026)
Background Benign prostatic hyperplasia (BPH) is a highly prevalent condition among aging men and a major cause of lower urinary tract symptoms (LUTS). Although α1-adrenoceptor blockers and 5-alpha-reductase inhibitors remain the cornerstone of treatment, their long-term use is frequently limited by adverse effects and suboptimal symptom control. Growing experimental and clinical evidence suggests that chronic prostatic inflammation plays a central role in BPH progression, raising interest in anti-inflammatory compounds such as curcumin. However, the clinical effectiveness of curcumin in BPH remains poorly defined. Methods We conducted a systematic review and meta-analysis of randomized and nonrandomized comparative studies evaluating curcumin versus placebo in men with BPH receiving α-blockers and/or 5-alpha-reductase inhibitors. Searches were performed in PubMed, Embase, and Cochrane CENTRAL. The primary outcome was change in International Prostate Symptom Score (IPSS). Secondary outcomes included prostate-specific antigen (PSA), prostate volume (PV), post-void residual volume (PVR), and maximum urinary flow rate (Q-max). Pooled analyses were performed using a random-effects model. Results Six studies involving 697 patients met the inclusion criteria. Compared with placebo, curcumin was associated with a significant improvement in IPSS (MD − 4.11; p = 0.0009), accompanied by reductions in PSA (MD − 0.52 ng/mL), PV (MD − 3.78 mL), and PVR (MD -2.38 mL), as well as an increase in Q-max (MD 2.09 mL/s). Subgroup analyses suggested greater symptomatic benefit among patients receiving α-blockers alone compared with those on combined α-blocker and 5-alpha-reductase inhibitor therapy. Substantial heterogeneity was observed across outcomes. Conclusion Curcumin supplementation was associated with significant improvement in LUTS and functional parameters in men with BPH. Although these findings support a potential adjunctive role for curcumin, the available evidence is limited by heterogeneity and study design variability. Well-designed, large-scale randomized trials are warranted to define its clinical utility, optimal formulation, and long-term effects.

Hidden beneath the arid Patagonian lowlands: ecological and conservation considerations to protect a hotspot of subterranean biodiversity - Marconi Souza-Silva; Hernán Augusto Iuri; Marcela Alejandra Mattioni; Robson de Almeida Zampaulo; Willians Porto; Gabriel Redonte; Mariana Paparas; Silvia Sicilia; Rodrigo Lopes Ferreira (Community Ecology, 2026)
To highlight the significance of unique subterranean ecosystems, the concept of Hotspots of Subterranean Biodiversity (HSB) was introduced to designate caves or cave systems with exceptionally high richness of cave-restricted species, which often require urgent conservation measures. The Cuchillo Curá cave system, the largest in Patagonia (Argentina) and the richest in cave-restricted fauna, exemplifies such a hotspot, although it remains poorly studied. In this review, we assess the richness of troglobitic species, identify environmental variables that shape their distribution, and highlight the conservation importance of the system. We documented 26 troglobitic and stygobitic species, combining direct sampling with published records. This fauna encompasses a broad taxonomic range, including Arachnida (8 species), Crustacea (6 species), Collembola (4 species), Diplura (3 species), and single representatives of Diplopoda, Symphyla, Coleoptera, Auchenorrhyncha, and Zygentoma. Most taxa are terrestrial (22), with only four aquatic representatives. Species distribution patterns were associated with microhabitat heterogeneity, distance from cave entrances, temperature, and relative humidity. Shelter diversity and thermal variation emerged as key predictors of species richness. The Cuchillo Curá system hosts a highly specialized subterranean fauna, marked by remarkable morphological and ecological adaptations to cave life. However, this fragile ecosystem is increasingly threatened by mining, tourism, groundwater depletion, and the advancing effects of climate change. Protecting the system is therefore essential not only for safeguarding Patagonia’s subterranean biodiversity but also for preserving a unique component of the region’s natural heritage.

Soil-relief-parent material relationship in a sequence of migmatite and gneiss in the semiarid Cariri region - Emanuel da Costa Cavalcante; Rodrigo Santana Macedo; Robson Vinício dos Santos; João Henrique Melo; Marcelo Metri Corrêa; Kalline de Almeida Alves Carneiro; Gabriel Ramatis Pugliese Andrade; Flávio Pereira de Oliveira; Antônio Augusto Sousa; Jean-Thomas Cornélis; Milton César Costa Campos (Geoderma Regional, 2026)

Spatial variability and source apportionment of particulate matter (PM2.5) in Rio de Janeiro: insights from Urban, preserved, and biomass burning areas - Luis Fhernando Mendonça da Silva; Hellen Gonçalves Vieira; Elizanne P. S. Justo; Ivan Víctor Silva Guillen; Rodrigo Stellet Ferreira; Vanessa A. dos Anjos; Ricardo Henrique M. Godoi; Maria Cristina Canela; Cibele Maria Stivanin de Almeida; Tatiana Dillenburg Saint’Pierre; Adriana Gioda (Journal of Atmospheric Chemistry, 2026)
Air pollution is a critical environmental issue influenced by both natural and anthropogenic sources. We hypothesized that PM 2.5 chemical composition varies spatially due to local anthropogenic sources, soil resuspension, and biomass burning. This study analyzed particulate matter (PM 2.5 ) concentrations and chemical composition (black carbon (BC), elements, and ions) in three locations in Rio de Janeiro state: Gávea (urban area), PARNASO (environmental preservation area), and Campos dos Goytacazes (urban with burning biomass). The results show that PM 2.5 concentrations varied significantly among the sampled sites, with the average highest values recorded in PARNASO (20 ± 13 µg m − 3 ), followed by Gávea (12 ± 7 µg m − 3 ), and Campos (8 ± 4 µg m − 3 ). Although no daily samples exceeded Brazilian air quality standards, 23% surpassed WHO guidelines. Fe and Al were the most abundant elements in all sites, indicating strong soil resuspension influence, with higher concentrations in Campos. BC was higher in PARNASO (2.2 ± 0.9 µg m − 3 ) but contributed more to PM 2.5 in Campos (22–24%), highlighting the biomass-burning influence. Water-soluble ions, particularly Cl − , Na + , SO 4 2− , and NO 3 − , were predominant across all sites, with K + showing statistical differences between seasonality in Campos. A Principal Component Analysis (PCA) identified soil resuspension, vehicular emissions, and biomass burning as major contributors to PM 2.5 pollution. These findings underscore the necessity for region-specific air quality policies and continuous monitoring, emphasizing their global relevance for effective long-term pollution mitigation in urban, and preserved areas.

Commercial graphene oxides show distinct suitability for silver-nanocomposite formation and antibiofilm activity and cytocompatibility - Thamyres Freire da Silva; Francisco Fábio Pereira de Souza; Thiago Alves de Moura; Luciano Ferreira de Almeida; Maria Rosiene Antunes Arcanjo; Antônio Gomes de Souza Filho; Adriano Lincoln Albuquerque Mattos; Juan Antonio Cecilia; Enrique Rodriguez-Castellon; Henry Kobs; Andreia Fonseca de Faria; Maria Kelva do Carmo; et al. (In vitro models, 2026)

Impact of Solubilized Mannan Oligosaccharide Supplementation on Growth Performance, Digestive Health, Stress Resistance, and Economic Efficiency in Pacific White Shrimp (Penaeus vannamei) Raised in an Intensive Synbiotic System - Danielle Alves da Silva; Flávia Abreu Everton; Gisely Karla de Almeida Costa; Suzianny Maria Bezerra Cabral da Silva; Fernando Leandro dos Santos; Rodrigo Antônio Ponce de Leon Ferreira de Carvalho; Giovani Sampaio Gonçalves; João Fernando Albers Koch; Luis Otavio Brito (Fishes, 2026)
The present study investigated how dietary inclusion of solubilized mannan oligosaccharide (MOS) influences growth performance, digestive health, stress resilience, and production profitability in Pacific white shrimp (Penaeus vannamei) reared under intensive synbiotic conditions. Juveniles averaging 3.00 ± 0.04 g were stocked at 100 shrimp m−2 and fed experimental diets containing 0 (control), 1.0, 2.0, or 4.0 g kg−1 MOS for 60 days. Shrimp receiving 1.0 g kg−1 MOS showed higher growth rate, improved feed conversion, and greater final body weight than the control (p

Dual inhibition of MMP-2 and actin dynamics by a novel bis-chalcone: an anticancer strategy for oral squamous cell carcinoma - Rodrigo Elísio de Sá; Bruna Oliveira de Almeida; Marcelo da Costa Mota; Matheus Pedrosa de Oliveira; Anali Del Milagro Bernabe Garnique; Keli Lima; Aline Bernardes Valeze; Jefferson Almeida Rocha; Caridad Noda Pérez; João Agostinho Machado Neto; Letícia Veras Costa Lotufo; José Delano Barreto Marinho Filho; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Oral squamous cell carcinoma (OSCC), accounts for approximately 90% of oral cancer cases, and due to its aggressive nature and limited treatment options remains a significant clinical challenge. In the pursuit of novel therapeutic agents, bis-chalcones (a subclass of chalcones) have emerged as promising candidates with multipronged anticancer potential. In this study, we synthesized and evaluated a novel bis-chalcone (B2OCH 3 ), for its cytotoxic, anti-migratory, anti-invasive, and anti-adhesive activities, as well as potential mechanisms of action. The compound was obtained via Claisen–Schmidt condensation and spectroscopically characterized. Cytotoxicity was assessed using MTT, pulse treatment, and trypan blue exclusion assays. Morphological changes were examined with panoptic staining and immunofluorescence. Clonogenic, migration, adhesion, and invasion assays were performed to assess anti-metastatic potential. Molecular docking and gene/protein expression analyses were conducted by quantitative PCR and Western blot. B2OCH 3 exhibited potent cytotoxicity against HSC-3, SCC-4, and CAL-27 OSCC cell lines, with HSC-3 being the most sensitive. The compound demonstrated selectivity for cancer cells as compared with non-tumor HS5 and HaCaT cells. Reduced viability was accompanied by mitotic figures and apoptotic bodies. B2OCH 3 significantly inhibited colony formation, migration, invasion, and adhesion in HSC-3 cells. Morphological analysis revealed modulation of actin filament organization and reduced filopodia formation. Molecular docking indicated MMP-2 and F-actin affinity, and was corroborated by molecular assays confirming protein modulation for both. Our findings identify B2OCH 3 as a promising therapeutic candidate for OSCC, highlighting its potential to simultaneously target both MMP-2 activity and actin cytoskeleton regulation.

Thermal and oxidative stress responses of Paecilomyces species recovered from beverage processing environments - Mailah Ali Abdul Rahman Mahfouz; Arthur Kael Rodrigues Pia; Rafaella Santos Mori Bragil; Naara Aparecida Almeida; Anderson S. Sant’Ana; Benedito Corrêa; Rodrigo Savio Pessoa; Liliana de Oliveira Rocha (World Journal of Microbiology and Biotechnology, 2026)

Production of an enzymatic cocktail by Aspergillus japonicus in a stirred-tank bioreactor for application in animal feed - Ana Lorena de Oliveira Simas; Aline Pereira Almeida; Nathalia Nunes Glienke; Quézia de Melo Santana; Rodrigo Mattos Silva Galeano; Charles Kiefer; Karina Márcia Ribeiro de Souza Nascimento; Maria de Lourdes Teixeira de Moraes Polizeli; Douglas Chodi Masui; Fabiana Fonseca Zanoelo; Giovana Cristina Giannesi (World Journal of Microbiology and Biotechnology, 2026)

Molecular detection of Escherichia coli virulence factors in swine isolates: A systematic review and meta-analysis - Elisa De Conti; Rodrigo C. Paiva; Brad Kuennen; Giovani Trevisan; Daniel C.L. Linhares; Annette M. O’Connor; Marcelo N. Almeida (Veterinary Microbiology, 2026)

Beyond intensity: An impact-based drought risk framework for the semi-arid Jequitinhonha River Basin, Brazil - Anna Flávia Almeida Perini; Jhones da Silva Amorim; Raíssa Nepomuceno Freitas; Rodrigo Perdigão Gomes Bezerra; Carlos Rogério de Mello; André Ferreira Rodrigues (Journal of Environmental Management, 2026)

Circular and Sustainable Business Model Innovation: Formulating an Integrated Concept Through A Systematic Literature Review - Andreza Rodrigues de Araujo; Rodrigo Marques de Almeida Guerra; David Lorenzi Junior; Jordana Marques Kneipp; Luísa Margarida Cagica Carvalho (Circular Economy and Sustainability, 2026)
Despite the significant growth in research on the triad of Circular Economy (CE), Innovation, and Sustainable Business Models (SBMs), theoretical fragmentation persists due to the lack of holistic conceptual integration, resulting in a heterogeneous framework that is difficult to apply in practice. Given this scenario, this study aimed to identify, categorize, and systematize the state of the art of Circular Economy, Innovation, and Sustainable Business Models, aiming to increase conceptual clarity and strengthen the application of these concepts in theory and practice. At the same time, we sought to map emerging trends, opportunities, challenges, and future directions capable of supporting the work of academics, practitioners, and public policymakers. To this end, we conducted a systematic literature review based on the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols, resulting in the final selection of 60 publications extracted from the Scopus database. The results suggest that research in this field is emerging, rapidly expanding, and with increasing diversity of applications across different contexts and sectors, although still concentrated in developed countries and at an early stage of scientific maturity, marked by the predominance of systematic reviews and case studies. A thematic evolution was also observed, moving from a focus on climate change and energy efficiency to encompass design principles, cross-sector collaboration, and sectors such as the bioeconomy and recycling, in addition to the more recent incorporation of digital technologies and consumer-focused strategies. Based on the analysis, the concept of Circular and Sustainable Business Model Innovation (CSIBI) is proposed, integrating the triad and systematizing its conceptual basis. The future research agenda covers strategies and metrics for sustainable circularity, as well as the role of digital technologies, governance, and human factors, providing guidance to consolidate the field. This framework contributes to the advancement of new research, strengthens the adoption of business practices in the transition to more circular and sustainable business models, and provides input for public policymakers, integrating the principles of the circular economy, innovation, and sustainable business models.

Phytotoxicity of Urochloa humidicola (Poaceae) root extract: a morphoanatomical and physiological approach - Rodrigo Barbosa Braga Feitoza; Maura Da Cunha; Gabriela de Almeida Marcato; Heitor Monteiro Duarte; Helena Regina Pinto Lima (Plant Biosystems, 2026)

Isolation of Candida maltosa strains able to achieve a high lipid productivity from malt bagasse hemicellulosic hydrolysate - Fernanda Pinheiro Moreira Freitas; Rodrigo Gonçalves Dias; Eduardo Luís Menezes de Almeida; Samuel Lessa Barbosa; Carina Aline Prado; Júlio César dos Santos; Silvio Silvério da Silva; Wendel Batista da Silveira (World Journal of Microbiology and Biotechnology, 2026)

Effect of age on the physicochemical quality of pork and fresh-style sausages from gilts and culled sows - Daniel Rodrigues Dutra; Ana Veronica Lino Dias; Erick Alonso Villegas-Cayllahua; Mateus Roberto Pereira; Érika Nayara Freire Cavalcanti; Thamiris Daiane Domenici; Igor Correia Lima; Leticia de Mattos Machado; Isabella da Luz de Souza; Aline Giampietro-Ganeco; Rodrigo Fortunato de Oliveira; Heloisa de Almeida Fidelis; et al. (Meat Science, 2026)

Genetic analysis of disqualifying traits in Nellore cattle - Fernanda Ripel Salgado; Amauri Felipe Evangelista; Juliana Cristina Sesana; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2026)

The recovery of forest structure 30 years after timber harvesting: a comparison of harvesting methods using field inventories and drone-based LiDAR data - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2026)

Evaluating an isotopic model for tracing the geographic origin of soybeans in Brazil - Maria Gabriella da Silva Araújo; Deoclecio Jardim Amorim; Rodrigo Figueiredo Almeida; Edmar Mazzi; Ana Claudia Gama Batista; Isabela Maria Souza-Silva; Alexandre Tadeu Brunello; Gabriela Bielefeld Nardoto; Gabriel J. Bowen; Luiz Antonio Martinelli (Food Chemistry, 2026)

Effects of soil nutrient enrichment on biomass, herbivores, and their predators differ between tree species in the Brazilian Cerrado - Carla Faleiro Tinoco; Sílvia Castro; Rodrigo Damasco Daud; Vanessa Leonel Falchi; Júlia Almeida Reis; Stefany Ribeiro Constantino; Carlos de Melo e Silva-Neto; Luísa Gigante Carvalheiro (Oecologia, 2026)
Human-induced changes in nitrogen (N) and phosphorus (P) global cycles and availability significantly impact plant growth and nutritional composition, thereby affecting ecosystem dynamics. However, research on the effects of increased nutrient availability often focuses on plant community-level effects, overlooking interspecific variability and neglecting impacts on higher trophic levels. Using a controlled fertilization experiment with six tree species that naturally occur in the Cerrado biome (Brazilian savannas), we showed that there is substantial interspecific variation in how plants respond to nutrient changes. This reflects the existence of competitive advantage for certain native species under a scenario of increased soil nutrient availability. Such effects propagated to higher trophic levels (herbivores and their predators), also varying between plant host species. The strength and direction of N input effect depended on P levels and the type of herbivores. Large invertebrate leaf herbivores were less affected than phytophagous mites. Impacts on higher trophic levels (predatory mites) were less pronounced than on phytophagous mites. Overall, we show that ongoing soil nutrient enrichment has the potential to alter interspecific competition dynamics in plant communities with consequences for ecological interaction partners. These findings have important implications for conservation and ecosystem management, especially in areas highly exposed to soil nutrient enrichment due to farming and industrial activities.

Performance-oriented parallel upscaling of river drainage networks for large data sets - Adriano Rolim da Paz; Rafael Lopes Mendonça; Ana Alice Rodrigues Dantas Almeida; Natalia Maria Mendes Silva; Rodrigo Cesar Lira da Silva (Computational Geosciences, 2026)
Extracting coarse-resolution river drainage networks from fine-resolution DEM or DTM is essential for large-scale hydrological and environmental modeling. Flow direction upscaling methods are preferred for preserving drainage patterns, but they face significant computational challenges when handling massive fine-resolution datasets. This study introduces eCOTAT + , an enhanced version of the COTAT + algorithm, designed to improve computational performance through two key strategies: (i) tile-based domain partitioning to reduce memory usage by processing localized subsets of data sequentially, and (ii) OpenMP-based parallelization to accelerate execution using multi-core processors. The eCOTAT + was applied to a 1-m LiDAR-derived DTM covering a 40× 40 km region in northeastern Brazil (1.6 billion pixels) and upscaling it to 100 m resolution. Twelve tiling configurations and eleven parallelization schemes (1–20 cores) were tested. Results showed that intermediate tile sizes (~ 20 × 20 coarse-resolution cells) offered the best trade-off between runtime and memory demands. Tiny tiles lead to high overhead from frequent memory and file operations, while large tiles diminish the advantages of parallelization. Parallelization significantly reduced runtime up to 8–12 cores, beyond which performance declined. A novel runtime-memory elasticity metric was proposed to quantify the balance between execution time and memory use across configurations. The upscaled drainage networks retained hydrological realism compared to the fine-resolution reference, confirming that computational optimizations did not compromise output quality. The eCOTAT + algorithm enables fast and scalable flow direction upscaling for both macro- and microscale applications, facilitating the use of massive elevation datasets even in standard computing environments.

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

Chemical investigation and evaluation of the antibacterial and antioxidant activities of ethanolic extracts from ten specimens of Cereus jamacaru DC. (Cactaceae) - Maria José Rejane Oliveira Almeida; José Jailson Lima Bezerra; Daniel Rodrigo Cavalcante de Araújo; Juliana Gomes Freitas; Fabiane Rabelo da Costa Batista; Bruno Oliveira de Veras; Márcia Vanusa da Silva; Francisco das Chagas Lima Pinto; Maria da Conceição de Menezes Torres (South African Journal of Botany, 2026)

Geophysical characterization of a sand deposit in a small-scale mining in the central east region of São Paulo State, Brazil - Jorge Luís Porsani; Victor Hugo Hott Costa; Nathália de Souza Penna; Rodrigo Corrêa Rangel; Marcelo Cesar Stangari; Gustavo Isnard Jarussi; Gabriel Alencar Silva Almeida Dantas; Rafael Josimar Araos Huaman (Journal of Applied Geophysics, 2026)

Do persistent mineralogical and geochemical signatures in highly weathered Oxisols reflect variations in basaltic lithotypes? - Elida Marina Nogueira; Vander de Freitas Melo; Rodrigo Studart Correa; Pablo Vidal-Torrado; Nádia Mariane Mucha; Jaime Antonio Almeida; Daniel Hanke; Jairo Calderari Oliveira Junior (CATENA, 2026)

Rural dogs (Canis familiaris) as sentinels to ectoparasites and tick borne pathogens around six Atlantic Forest conservation units in Brazil - Pedro Henrique Cotrin Rodrigues; Nelson Henrique de Almeida Curi; Elizabete Pereira Barbosa; Guilherme Ramos Demétrio; Ana Maria Oliveira Paschoal; Rodrigo Lima Massara; Adriano Garcia Chiarello; Marcelo Passamani; Camila Stefanie Fonseca de Oliveira; Daniel Sobreira Rodrigues; Júlia Angélica Gonçalves Silveira (Veterinary Parasitology, 2025)

Biodiversification with perennial forages increases soil carbon stocks and soybean yield - Larissa de Souza Bortolo; Victória Santos Souza; Rodrigo Estevam Munhoz de Almeida; Dener Márcio da Silva Oliveira; Lucas Pecci Canisares; Lucas Freitas Nogueira Souza; Maurício Roberto Cherubin (Agriculture, Ecosystems & Environment, 2025)

Petrogenesis and emplacement of the Paleoproterozoic A-type Marajoara granite in the Carajás province, southeastern Amazonian craton: Constraints from geochemistry, zircon geochronology, Nd Hf isotopes, coexistence of reduced and oxidized magmas and new insights from a composite dike - Rodrigo Fabiano Silva Santos; Davis Carvalho de Oliveira; José de Arimatéia Costa de Almeida; Roberto Dall'Agnol; Bhrenno Marangoanha; Marco Antonio Galarza; Cláudio Nery Lamarão; Fernando Fernandes da Silva (Lithos, 2025)

Effect of heat stress on estimates of genetic parameters for tick count in Hereford × Nelore cattle in Brazil - João Felipe do Nascimento Sampaio; Denyus Augusto de Oliveira Padilha; Rafaela Martins; Laila Talarico Dias; Rodrigo de Almeida Teixeira (Tropical Animal Health and Production, 2025)

The maintenance conditions of the zebrafish (Danio rerio) breeding stock affect the survival and behavior of their offspring - Francieli Ubirajara India Amaral; Aline Pompermaier; Gabriela Rutikoski; Milena Zanoello Bertuol; Paola Aparecida de Almeida; Luciane Dallazari da Silva do Prado; Wagner Antonio Tamagno; Jennifer L. Freeman; Rodrigo Egydio Barreto; Leonardo José Gil Barcellos (Applied Animal Behaviour Science, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Integrated 3D forward stratigraphic and basin modeling of the Santos Basin, offshore Brazil: Implications of sedimentary depositional facies and CO2 migration for silicification of continental carbonate reservoirs - Alina-Berenice Christ; Marie-Christine Cacas-Stentz; Nathalie Collard; Fadi Henri Nader; Elisabeth Bemer; Rodrigo Brandão Bunevich; João Paulo Borges Gomes; Olinto Gomes de Souza; Maria Anna Abreu de Almeida dos Reis (Marine and Petroleum Geology, 2025)

Sensor detection of shelf life: a multi-technique food analytical platform for mushroom analysis - Patricia Yukari Saiki; Fernando Cesar Rufino; Cassio Roberto de Almeida; Geovana Manzan Sales; Arthur Noin de Oliveira; Dunieskys Roberto Gonzalez Larrude; Ricardo Cotrin Teixeira; José Alexandre Diniz; Rodrigo Ramos Catharino (Food Research International, 2025)

Natural regeneration responses of tree species at the end of the first timber harvesting cycle in the Eastern Amazon - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2025)

The effect of turbidity on predator–prey interactions between invasive fish species - Rodrigo Fernandes; Fernando Mayer Pelicice; Eveline de Almeida Ferreira; Carlos Walker Fernandes Menezes; Victor Neudo Santos Tavares (Environmental Biology of Fishes, 2025)

Integrated assessment of water quality: influence of physicochemical parameters and ecotoxicological impacts under different flow conditions of lonqueador river, Southern Brazil - Clisley Marielly Ribeiro Lameira; Anna Karolina Gomes Oliveira; Daniela Carolina Antes; Cassiano Aparecido de Souza; Patricia Aline Bressiani; Mariah Pereira Rosa da Silva; Ana Carolina Pires Moreira; Ana Paula de Oliveira Schmitz; Juan Carlos Pokrywiecki; Ticiane Sauer Pokrywiecki; Fernando César Manosso; Eduardo Michel Vieira Gomes; et al. (Ecotoxicology, 2025)

Assessing the decarbonisation potential of light-duty vehicle fleet electrification in Brazil - Heinrich Gustave Herzog; Rodrigo Flora Calili; Maria Fatima Ludovico de Almeida (Transportation Research Part D: Transport and Environment, 2025)

In vitro effects of the new antifungal compound manogepix (APX001) against the three most clinically relevant species of Sporothrix - Fernando Almeida-Silva; Fernanda Praça Nogueira Marques; Pedro Henrique Tenório-Alvarenga; Vanice Rodrigues Poester; Melissa Orzechowski Xavier; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2025)

Metabolic brain changes in post-acute COVID-19: systematic review and meta-analysis of [18F]-FDG-PET findings - Izabella Fernanda Bastos Siqueira; Lais Almeida Figueiredo; Camila Emanuele Moreira Fernandes; Leandro Pinheiro Cintra; Glauber Fernandes de Oliveira; Maria Angélica Rios; Ricardo Maciel; Rodrigo Ferretjans; Nathalia Sernizon Guimarães; Luiz Alexandre Viana Magno (Brain Structure and Function, 2025)

Analysis of the ecotoxicity of waste generated in a laundry in the textile center of the Agreste region of Pernambuco using zebrafish (Danio rerio) as a bioindicator - Paula Raíza Alves Cavalcante; Jadson Freitas da Silva; Renatta Priscila Ferreira Silva; Matheus Victor Viana de Melo; Maria Letícia Santos Carnaúba da Silva; Maria Eduarda Borges de Almeida; Samara da Silva Gomes; Yuri Mateus Lima de Albuquerque; Rodrigo Cândido Passos da Silva; Pabyton Gonçalves Cadena; Rosângela Gomes Tavares (Environmental Science and Pollution Research, 2025)

Artificial intelligence-based optimization of the WEEE reverse chain in São Paulo − Brazil to promote economic, environmental and social benefits - Geraldo C.de Oliveira Neto; Rodrigo Neri Bueno da Silva; Gustavo Araújo Lima; Sidnei Alves de Araújo; Peterson Adriano Belan; Denilson Carvalho; Cecília M.V.B. Almeida (Journal of Cleaner Production, 2025)

Genomic-assisted selection to guide mate allocation and leverage hybrid vigor in Coffea canephora - Rodrigo Barros Rocha; Matheus Massariol Suela; Marcone Comério; Elaine M. Riva Souza; João Felipe Brites Senra; Maria Amélia G. Ferrão; Romário G. Ferrão; Aymbiré F. Almeida da Fonseca; Abraão Carlos Verdin Filho; Paulo Sérgio Volpi; Luis Felipe V. Ferrão (Tree Genetics & Genomes, 2025)

Soil carbon and nutrient stocks under intensified pasture and sugarcane expansion - Luiza Pecci Canisares; Eduardo Mariano; Adibe L. Abdalla-Filho; Lucas P. Canisares; Mauricio C. A. Leite; Maria G. S. Araújo; Rodrigo F. Almeida; Taciana F. Gomes; Érika S. P. B. Saldanha; Luiz A. Martinelli (Nutrient Cycling in Agroecosystems, 2025)

Metformin Improves Spatial Memory and Reduces Seizure Severity in a Rat Model of Epilepsy and Alzheimer’s Disease comorbidity via PI3K/Akt Signaling Pathway - Suélen Santos Alves; Letícia Rossi; Jose Antonio Cortes de Oliveira; Gabriel Servilha-Menezes; Mariana Grigorio-de-Sant’Ana; Rodrigo Focosi Mazzei; Sebastião Sousa Almeida; Adriano Sebollela; Rui Milton Patrício da Silva Junior; Norberto Garcia-Cairasco (Molecular Neurobiology, 2025)

Stable isotopic differences ( δ 13 C and δ 15 N ) between muscle and fin ray tissues from juvenile Atlantic goliath grouper Epinephelus itajara (Lichtenstein, 1822) using non‐lethal sampling - Ester F. Barbosa; Rodrigo F. Bastos; Lorena L. Almeida; Rafael L. Oliveira; Sabrina R. Vollrath; Alexandre M. Garcia; Mauricio Hostim‐Silva; Mario V. Condini (Journal of Fish Biology, 2025)
The Atlantic goliath grouper ( Epinephelus itajara ) is the largest species of grouper in the Atlantic Ocean and is classified as critically endangered in Brazil. This study compared the isotopic ratios of carbon (δ 13 C) and nitrogen (δ 15 N) between the muscle tissue and dorsal‐fin rays of 37 juveniles to assess fin rays as a non‐lethal alternative to muscle tissue sampling. The δ 13 C values in rays were significantly higher than those found in muscle, whereas the δ 15 N values did not differ significantly between tissues. Both stable isotopes showed high Spearman correlation coefficients (>0.80) between tissues. Thus, the study can enhance future research and broaden the application of stable isotope techniques in a non‐lethal manner.

Exploring pectin and retrograded starch microparticles as carriers for pomegranate peel bio-input in the treatment of Staphylococcus aureus infections - Soraya Dias Saleme; Mikaela Vieira Beloni; Rita Cristina Gonçalves de Melo; Suzana Gonçalves Carvalho; Rodrigo de Almeida Romagna; Elias Werner; Mário Ferreira Conceição Santos; Marlus Chorili; Rodrigo Resende Kitagawa; Juliana Alves Resende; Janaina Cecília Oliveira Villanova (Natural Product Research, 2025)

Partial laryngectomy in a cat with thyroid cartilage osteochondroma: Surgical management and postoperative care - Paloma Helena Sanches da Silva; Luíza Bortolotti de Carvalho; Pedro Antônio Bronhara Pimentel; Isabella Oliveira Almeida; Bruna Voltolin de Sena; Paula Baêta da Silva Rios Turquete; Tatiana Geraissate Gorenstein; Eutálio Luiz Mariani Pimenta; Bruno Ferrante; Patrícia Maria Coletto Freitas; Rodrigo dos Santos Horta (Topics in Companion Animal Medicine, 2025)

Droughts, livestock expansion, and Forest degradation: A 37-year assessment of landscape change in a semiarid municipality of Brazil - Francisco Éder Rodrigues de Oliveira; Eveline de Almeida Ferreira; Rodrigo Fernandes; Victor Neudo Santos Tavares; Yara de Almeida Araújo; João Luiz Lima; Luiz Fernando de Sousa Antunes; Noely Raiana da Costa Chagas; Pedro Lucas Nogueira de Freitas; Cirley Tavares Lemos; Ayslan do Nascimento Fernandes; Eulene Francisco da Silva (Science of The Total Environment, 2025)

Probing the role of calcium carbonate on hydrothermal liquefaction of polyethylene in the presence of supercritical water - Kalsoom Jan; Daniel Lachos Perez; Akash Patil; Rodrigo Almeida Luciano; Débora M. Vaz de Miranda; Wan-Ting Chen (Chemical Engineering Journal, 2025)

Review of Records and Hypotheses of Giant Tiger Shrimp (Penaeus monodon) Introduction in Brazil - Jhonatas Teixeira Viana; Juliana Oliveira de Freitas; Túlio Ésio Ferreira do Nascimento; Flavio de Almeida Alves-Júnior; Rubens Galdino Feijó; Rodrigo Maggioni (Thalassas: An International Journal of Marine Sciences, 2025)

Ketamine-Ethanol Combination Decreases Reduced Glutathione Levels and Activates both Intrinsic and Extrinsic Apoptotic Pathways Prior to Neuronal Death in SH-SY5Y Cells - Felype Valentim Duarte Castelhano; Carolina Aparecida de Faria Almeida; Giulia de Assis Braz; Gabriela Otofuji Pereira; Rafaela Yolanda Silvino de Almeida; Matheus Lujan Pereira; Juliana Ligia Freires Ribeiro; Karin Argenti Simon; Rodrigo Portes Ureshino; Tania Marcourakis; Larissa Helena Torres; Raphael Caio Tamborelli Garcia (Neurotoxicity Research, 2025)

Snow-Deposition Characteristics from X-Band Polarimetric SAR and Geospatial Analysis at Union Glacier, Antarctica - Christian Florian Göbel; Jorge Arigony-Neto; Ricardo Jaña; Rodrigo Gomez-Fell; Jean de Almeida Espinoza; Francisco Fernandoy; Ian D. Goodwin (Journal of the Indian Society of Remote Sensing, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Nosocomial transmission of Sporothrix brasiliensis in two cats - Rafael Gariglio Clark Xavier; Salene Angelini Colombo; Brendhal Almeida Silva; Jéssica Rabelo de Oliveira Persichini; Gabriele Silva Duarte; João Victor Ferreira Campos; Rodrigo Otávio Silveira Silva; Maria Isabel de Azevedo (Topics in Companion Animal Medicine, 2025)

On Anacroneuriini (Plecoptera: Perlidae) morphology: Standardizing vocabulary and a morphological atlas - Rodrigo Braga Gastaldo; Lucas Henrique de Almeida; Frederico Falcão Salles (Arthropod Structure & Development, 2025)

Influence of different environmental challenges on the expression of productive traits in Holstein cattle in the southern region of Brazil - Rafaela Martins; Ivan Carvalho Filho; Altair Antônio Valloto; Roberto Carvalheiro; Lucia Galvão de Albuquerque; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2025)

Assessing Impact of Food on Oral Drug Bioequivalence Supporting ICH M13 A with the Advancements of Physiologically Based Pharmacokinetic Modeling - Arindom Pal; Khondoker Alam; Ethan Stier; Tycho Heimbach; Rodrigo Cristofoletti; Jozef Al‐Gousous; Peter Langguth; Rebeka Žakelj; Tausif Ahmed; Susana Almeida; Jianghong Fan; Vidula Kolhatkar; et al. (Pharmaceutical Research, 2025)

Feeding rate for newly weaned tambaqui (Colossoma macropomum) juveniles in a recirculating aquaculture system - Bruno José Corecha Fernandes Eiras; Paola Fabiana Fazzi Gomes; Debora Sayumi Doami Melo; Jhonas Warlenson Palheta Nobre; Helen Cristiane Araújo Souza; Marcela Cardoso Sena; Joane Natividade; Igor Hamoy; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; André Luiz Alves de Sá; Rodrigo Takata; et al. (Animal Feed Science and Technology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Passive sampling-derived aqueous concentrations of organotins and booster biocides in the largest Port of South America (Southeastern Brazil) - Alan Carlos de Almeida; Rodrigo Moço Batista; Ítalo Braga Castro; Gilberto Fillmann (Water Research, 2025)

Assessment of water and sediment quality in intermittent streams across different land uses in the Brazilian semiarid region: implications for sustainable irrigation and resource management - Yara de Almeida Araújo; Eveline de Almeida Ferreira; Rodrigo Fernandes; Gustavo Gonzaga Henry-Silva; Francisco Éder Rodrigues de Oliveira; Victor Neudo Santos Tavares; Jeane Cruz Portela; Marx Lima da Cunha; Noely Raiana da Costa Chagas; Luiz Fernando de Sousa Antunes; Antônio Gustavo de Luna Souto; Eulene Francisco da Silva (Environmental Science and Pollution Research, 2025)

Guanandi (Calophyllum brasiliense) seed vegetable oil: Characterization, in vitro safety, and feasibility of use as a pharmaceutical bioinput - Gabriel Mendes da Cunha; Nayhara Madeira Guimarães; Rodrigo de Almeida Romagna; Ramon Campos Vieira; Larissa Kéllen Ferreira; Marcelo Ferreira Golvim Filho; Juliana Aparecida Severi; Ricardo Machado Kuster; Eduardo Frizzera Meira; Rodrigo Rezende Kitagawa; Cristiane dos Santos Giuberti; Janaina Cecilia Oliveira Vilanova (Next Research, 2025)

Chemical profile, antioxidant, antifungal, and cytotoxic activities of propolis from the stingless bee Tetragona clavipes - Ariane Pinheiro Cruz Bergamini; Brendo Victor Siqueira de Almeida Bergamini; Iana Soares Pessoa; Thiago Antônio de Sousa Cutrim; Tamires Cruz dos Santos; Matheus Campos dos Santos; Victor da Rocha Fonseca; Wanderson Romão; Rodrigo Scherer; Denise Coutinho Endringer; Marcio Fronza (Brazilian Journal of Microbiology, 2025)

New records of peppermint shrimps from northeastern Brazil support Lysmata lipkei as junior synonym of Lysmata dispar - Rodrigo Guéron; J. Antonio Baeza; Gabriel Lucas Bochini; Mariana Terossi; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2025)

Genetic parameters for the occurrence of bovine viral diarrhea virus in Holstein cattle in Brazil - Simone Soares da Silva; Denyus Augusto de Oliveira Padilha; Altair Antônio Valloto; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Livestock Science, 2025)

Enhancing bioremediation of diesel/biodiesel blend (B20) impacted sites using in situ bioreactors: A nature-based solution for sustainable groundwater management - Marcio Roberto Schneider; Ana Claudia Canalli Bortolassi; Adriana Ururahy Soriano; Marcus Paulus Martins Baessa; Luiz Fernando Martins; Rodrigo de Almeida Heringer; Admir José Giachini (Groundwater for Sustainable Development, 2025)

Electromyography and oculomotricity as markers of benzocaine anesthesia in juvenile tambaqui (Colossoma macropomum) - Alex da Silva Lobão de Souza; Rodrigo Yukihiro Gimbo; Suzane Maia da Fonseca; Raimundo Aderson Lobão de Souza; Luis André Luz Barbas; Moisés Hamoy; Daniela Volcan Almeida (Aquaculture, 2025)

Estimation of genetic parameters for racing time and ranking in Thoroughbred horses - Denyus Augusto de Oliveira Padilha; Suelen Fernandes Padilha; Rafaela Martins; Bruna Elisa Machado Scheffer; Mayumi Regina Miliorini; Laila Talarico Dias; Rodrigo de Almeida Teixeira (Journal of Equine Veterinary Science, 2025)

Clover in vineyards, a potential trap plant for the mealybug Pseudococcus calceolariae—a vector of GLRaV-3 to grapevines but not clover species - Rebecca Gough; Kar Mun Chooi; Manoharie Sandanayaka; Vicky Davis; Duncan Hedderley; Tara Taylor; Daniel Cohen; Cecilia A. Prator; Rodrigo P. P. Almeida; Vaughn A. Bell; Robin M. MacDiarmid (Journal of Pest Science, 2025)
Grapevine leafroll disease (GLD) affects grapevines worldwide. The primary causal agent of GLD is grapevine leafroll-associated virus 3 (GLRaV-3), which spreads to uninfected grapevines via mealybugs and soft-scale insects. Pseudococcus calceolariae (Hemiptera: Pseudococcidae) is a mealybug vector of GLRaV-3 in New Zealand. P. calceolariae also colonizes clovers ( Trifolium spp.) growing naturally as vineyard ground cover. Separating mealybug from GLRaV-3 grapevine host could be enhanced by a trap plant: an alternative host attractive to and retentive of the target pest. We evaluated the association between P. calceolariae and ‘Grasslands Huia’ white clover (GHWC). GHWC seed was sown under grapevines in a commercial vineyard (14 × 0.4 ha plots); the control was under-vine herbicide use (7 × 0.4 ha plots, where only few Trifolium spp. plants grew). After 2 years, GHWC cover peaked at 40% mealybug infestation in 2019. From 2018 to 2021, P. calceolariae detection and abundance on GHWC was significantly higher than plants from the control plots. There was no treatment effect for mealybug infestation of grapevine leaves nor of GLRaV-3 incidence, independent of vintage. A glasshouse trial found no transmission of GLRaV-3 by P. calceolariae to any of 256 plants among five clover cultivars tested ( Trifolium spp.), including GHWC; mealybug transmitted GLRaV-3 to 35 of 107 Nicotiana benthamiana plants. The results showed that in the 5-year period, added GHWC did not decouple P. calceolariae from the grapevine to reduce GLRaV-3 incidence, but rapid colonization of GHWC by mealybug and the lack of GLRaV-3 transmission to GHWC are encouraging. Further evaluation is needed to assess whether plant biodiversity can benefit a GLRaV-3 ecological management objective.

A pathway for decreasing the water footprint from grazing-based beef production systems in the Tropics - Mariana Pereira Barsotti; Roberto Giolo de Almeida; Manuel Claudio Motta Macedo; Rodrigo da Costa Gomes; Julio Cesar Pascale Palhares; Andre Mazzetto; Uta Dickhoefer (Agricultural Systems, 2025)

Life history differences enhance invasiveness and syntopic distribution: a comparative study with three congeneric marine species along Southwest Atlantic coast - Mauricio Peixoto Scapolatempore; Rodrigo Soares Pessanha D’Almeida; Tarço de Meneses Macedo Costa; Fabio Bettini Pitombo (Biological Invasions, 2025)

Effects of dietary nucleotides on performance, proximate composition, health status, nitrogen stress resistance, and return on investment for Pacific white shrimp, Penaeus vannamei, raised in an intensive synbiotic system - Danielle Alves da Silva; Katharine Batista Santos de Souza; Gisely Karla de Almeida Costa; Suzianny Maria Bezerra Cabral da Silva; Fernando Leandro dos Santos; Rodrigo Antônio Ponce de Leon Ferreira de Carvalho; Giovanni Sampaio Gonçalves; João Fernando Albers Koch; Luis Otavio Brito (Aquaculture International, 2025)

Herbicides and bio-inputs: Compatibility and challenges for sustainable agriculture - Tayna Sousa Duque; Rodrigo Almeida Pinheiro; Iasmim Marcella Souza; Gabriele Gonçalves Silva; Marcus Alvarenga Soares; José Barbosa dos Santos (Chemosphere, 2024)

Emerging contaminants as indicators of short-term environmental changes in an eutrophicated coastal lagoon - Izabella Almirante Porto Tiburcio Rodrigues; Milena Ceccopieri; Rodrigo Chiclana; Letícia Tessaro; Regina Fonseca Almeida; Diana Moreira; Carlos German Massone (Marine Pollution Bulletin, 2024)

Resilience patterns in the analysis of social-ecological networks of small-scale fishing in a subtropical estuarine system - Michele Cristina Nether; José Milton Andriguetto-Filho; Mauricio Almeida Noernberg; André Pereira Cattani; Isabeli Cristina Gomes Mesquista; Rodrigo Pereira Medeiros; Carlos Schneider Batista; José Hugo Dias Godim Guanais; Paulo da Cunha Lana; Maikon Di Domenico (Ocean & Coastal Management, 2024)

Trophic ecology and habitat use of an overexploited commercial snapper (Lutjanus jocu) in a tropical nursery estuary elucidated by stable isotopes - Patrick Derviche; Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Sabrina R. Vollrath; Marcelo Soeth; Alexandre M. Garcia; Maurício Hostim–Silva (Regional Studies in Marine Science, 2024)

Life-history updates and stock assessment of Macrodon atricauda (teleostei, sciaenidae) from southern Brazil - Eidi Kikuchi; Luis Gustavo Cardoso; Rodrigo Sant'Ana; Bruno L. Mourato; Maíra de Sousa Almeida; Manuel Haimovici (Regional Studies in Marine Science, 2024)

The spermidine promotes maturation and tissue differentiation of somatic embryos of Euterpe edulis Martius, an endangered Atlantic Forest species - Joana Silva Costa; Tamyris de Mello; Débora Pellanda Fagundes; Tatiane Dulcineia Silva; Caroline Palacio de Araujo; Ingridh Medeiros Simões; Mariana Ribeiro de Almeida; Eduardo Santos Cade; João Pedro Vieira Fraga de Assis; Edilson Romais Schmildt; Wagner Campos Otoni; Amir Ali Khoddamzadeh; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Treatment of metastatic apocrine sweat gland adenocarcinoma in a cat with association of surgical resection and angular oris reconstruction, extensive lymphadenectomy, electrochemotherapy and systemic chemotherapy - Pedro Antônio Bronhara Pimentel; Isabella Oliveira Almeida; Bruna Voltolin de Sena; Sarah Kowalczyk; Geovanni Dantas Cassali; Rodrigo dos Santos Horta (Topics in Companion Animal Medicine, 2024)

Climatic fluctuations alter the preference of stingless bees (Apidae, Meliponini) towards food contaminated with acephate and glyphosate - Lívia Maria Negrini Ferreira; Michael Hrncir; Danilo Vieira de Almeida; Rodrigo Cupertino Bernardes; Maria Augusta Pereira Lima (Science of The Total Environment, 2024)

Water level regime variation is a crucial driver for taxonomic, functional, and phylogenetic diversity in seasonally flooded tropical forests - Fernanda Moreira Gianasi; Vinícius de Andrade Maia; Aline Meyer Oliveira; Patrícia Vieira Pompeu; Cléber Rodrigo de Souza; Camila Laís Farrapo; André Maciel da Silva-Sene; Fernanda de Oliveira; Thiago Magalhães Meireles; Ana Lívia de Carvalho Rodrigues; Denise Moura Madeira; Felipe Carvalho Araújo; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Correction to: Influence of different environmental challenges on the expression of reproductive traits in Holstein cattle in Southern Brazil - Rafaela Martins; Bárbara Mazetti Nascimento; Altair Antônio Valloto; Roberto Carvalheiro; Lucia Galvão de Albuquerque; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2024)

Influence of different environmental challenges on the expression of reproductive traits in Holstein cattle in Southern Brazil - Rafaela Martins; Bárbara Mazetti Nascimento; Altair Antônio Valloto; Roberto Carvalheiro; Lucia Galvão de Albuquerque; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2024)

Loop-Mediated Isothermal Amplification for the Diagnosis of Sporotrichosis by Sporothrix brasiliensis - Marcella Donadel Araujo; Vanice Rodrigues Poester; Helena Schirmer; Vanessa Suñe Mattevi; Mariana Rodrigues Trápaga; Melissa Orzechowski Xavier; Marcus de Melo Teixeira; Rodrigo Almeida-Paes; Rosely Maria Zancopé-Oliveira; Cecília Bittencourt Severo (Mycopathologia, 2024)

Influence of precipitation and temperature on burned areas in the agricultural and cattle ranching frontier of the Brazilian Amazon - Rodrigo Martins Moreira; Ruan Almeida Martins (Environmental Monitoring and Assessment, 2024)

A Cluster of Diutina catenulata Funguria in Patients with Coronavirus Disease 2019 (COVID-19) Hospitalized in a Tertiary Reference Hospital from Rio de Janeiro, Brazil - Rodrigo Almeida-Paes; Marcus de Melo Teixeira; Fernanda Alves de Oliveira; Marcos de Abreu Almeida; Fernando Almeida-Silva; Kim Mattos Geraldo; Estevão Portela Nunes; Bridget M. Baker; Jason E. Stajich; Beatriz Grinsztejn; Valdilea Gonçalves Veloso; Andrea d’Avila Freitas; et al. (Current Microbiology, 2024)

Competitive response of maize against glyphosate-resistant Digitaria insularis and Eleusine indica - Matheus de Freitas Souza; Jonas Rodrigo Henckes; Luiz Henrique Saes Zobiole; Rubem Silvério de Oliveira; Guilherme Braga Pereira Braz; Jamil Constantin; Fellipe Goulart Machado; Adriana Almeida do Amarante; Camila Jorge Bernabé Ferreira (Crop Protection, 2024)

The invasive Bedellia somnulentella (Lepidoptera: Bedelliidae): new record of host plant, predator and biome in Brazil - Rodrigo Almeida Pinheiro; Maria Jéssica dos Santos Cabral; Samuel Cunha Oliveira Giordani; Marcos Magalhães de Souza; Philipe Guilherme Corcino Souza; José Cola Zanuncio; José Barbosa dos Santos; Marcus Alvarenga Soares (Phytoparasitica, 2024)

Host finding and probing behavior by Philaenus spumarius on olive varieties with a different degree of susceptibility to Xylella fastidiosa - Daniele Cornara; Valentina Zaffaroni-Caorsi; Zeinab Hamouche; Sabina Avosani; Giuseppe Cavallo; Vincenzo Verrastro; Clara Lago; Antonio Trani; Angelo De Stradis; Rodrigo P. P. Almeida; Alberto Fereres (Journal of Pest Science, 2024)
Abundance on and access time to the host plant are the pivotal factors in Xylella fastidiosa transmission to olive by the meadow spittlebug Philaenus spumarius . Therefore, olive varieties suitable for the vectors, i.e., plants providing all the necessary cues to the insect for their location, settling and acceptance, and devoid of antixenotic defenses, could be more susceptible to infection than varieties non- or less suitable for the vector. Here we evaluated whether a bacterium-susceptible olive variety, Ogliarola Salentina, could be a more suitable host for P. spumarius than the two resistant varieties Leccino and FS-17. We carried out: (i) an evaluation of between-hosts and within-host preference; (ii) an insect survival analysis; (iii) an Electrical Penetration Graph (EPG)-assisted analysis of the probing behavior; (iv) light microscopy of the tissues the spittlebugs had access to; (v) an analysis of the xylem sap primary metabolites. In choice tests, the insect exhibited a significant preference for Ogliarola Salentina. In addition, spittlebugs displayed longer xylem sap ingestion bouts on the bacterium-susceptible variety compared to resistant genotypes, possibly because of differences in the xylem sap chemical profile rather than xylem anatomy. Spittlebugs preference for Ogliarola over both Leccino and FS-17 could be a relevant and so far overlooked component of the low disease prevalence in these two olive varieties reported in Southern Italian olive orchards. Overall, our data point toward the importance of incorporating studies on vector-plant interaction and host traits of resistance to the vector in research on genotypes resistant to X. fastidiosa .

Use of crude glycerin in dairy goat feeding and its effects on milk and cheese performance and quality - Rodrigo Barbosa de Andrade; Kelly Cristina dos Santos; Érica Carla Lopes da Silva; Edneide Rodrigues da Silva; Michel do Vale Maciel; João Paulo Ismério dos Santos Monnerat; Dorgival Morais de Lima Júnior; Neila Mello dos Santos Cortez; Maria Gabriela da Conceição; Susana Paula Almeida Alves; Rui José Branquinho de Bessa; Francisco Fernando Ramos de Carvalho (Animal Feed Science and Technology, 2024)

Sex dimorphism in pupae and adults of the specialist Ipomoea batatas defoliator Bedellia somnulentella (Lepidoptera: Bedelliidae) - Rodrigo Almeida Pinheiro; Maria Jéssica dos Santos Cabral; Samuel Cunha Oliveira Giordani; José Cola Zanuncio; José Eduardo Serrão; Conceição Aparecida dos Santos; Marcus Alvarenga Soares (Neotropical Entomology, 2024)

An alternative silicone-based passive sampling device to derive organotin concentrations in the aqueous phase - Alan Carlos de Almeida; Rodrigo Moço Batista; Gilberto Fillmann (Chemosphere, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Regolith mapping using airborne gamma-ray spectrometry in central Brazil - Gustavo Rosa de Almeida; Adriana Maria Coimbra Horbe; Sanclever Freire Peixoto; Darby Pereira Dantas de Lima; Rodrigo dos Reis Salles (Journal of South American Earth Sciences, 2024)

Dynamics of experimental plantations of Tachigali vulgaris in response to fertilization and soil texture - Roberthi Alef Costa Teixeira; Michael Douglas Roque Lima; Arystides Resende Silva; Delman de Almeida Gonçalves; Leo Jakson da Silva Moreira; Rodrigo Otávio Veiga de Miranda; Ananias Francisco Dias Junior; Mario Tomazello-Filho; Alvaro Augusto Vieira Soares; Thiago de Paula Protásio (New Forests, 2024)

Nitrogen limitation in eucalypt roots: a cascading influence on the mobilization of soil organic matter - Luis Carlos Colocho Hurtarte; Ivan Francisco Souza; Rodrigo Teixeira Ávila; Luís Fernando J. Almeida; Gabriela Soares; Leonardus Vergütz; Ivo Ribeiro Silva (Biology and Fertility of Soils, 2024)

Validation of an FT-IR microscopy method for the monitorization of microplastics in water for human consumption in Portugal: Lisbon case study - Rodrigo D. M. Cordeiro; Vítor V. Cardoso; Rui N. Carneiro; Cristina M. M. Almeida (Environmental Science and Pollution Research, 2024)

Mesenchymal stem cell-derived cell-free technologies: a patent landscape - Luiza Carolina França Opretzka; Cláudio Damasceno Pinto; Jânio Rodrigo de Jesus Santos; Alyne Almeida de Lima; Milena Botelho Pereira Soares; Cristiane Flora Villarreal (Biotechnology Letters, 2024)

Seeing further into the early steps of the endangered atlantic goliath grouper (Epinephelus itajara): Eye lenses high resolution isotopic profiles reveal ontogenetic trophic and habitat shifts - Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Alexandre M. Garcia; Maurício Hostim-Silva (Marine Environmental Research, 2024)

Genetic parameters for mesenteric torsion in a pig maternal line - Suelen Fernandes Padilha; Amauri Felipe Evangelista; Luis Orlando Duitama Carreño; Marcelo Silva Freitas; Jader Silva Lopes; Adriana Mércia Guaratini Ibelli; Jane de Oliveira Peixoto; Marcos Antônio Zanella Morés; Maurício Egídio Cantão; Mônica Corrêa Ledur; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Livestock Science, 2024)

In vitro activity of the anthelmintic drug niclosamide against Sporothrix spp. strains with distinct genetic and antifungal susceptibility backgrounds - Mariana Lucy Mesquita Ramos; Fernando Almeida-Silva; Vanessa Brito de Souza Rabello; Juliana Nahal; Maria Helena Galdino Figueiredo-Carvalho; Andrea Reis Bernardes-Engemann; Vanice Rodrigues Poester; Melissa Orzechowski Xavier; Wieland Meyer; Rosely Maria Zancopé-Oliveira; Susana Frases; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2024)

Agroforestry can improve soil fertility and aggregate-associated carbon in highland soils in the Brazilian northeast - Rodrigo Santana Macedo; Letícia Moro; Cristiano dos Santos Sousa; Kalline de Almeida Alves Carneiro; Milton César Costa Campos; Alexandre Pereira de Bakker; Raphael Moreira Beirigo (Agroforestry Systems, 2024)

Ants (Hymenoptera: Formicidae) in subterranean natural cavities of Minas Gerais, Brazil - Natalia Ladino; Rodrigo M. Feitosa; Robson de Almeida Zampaulo; John E. Lattke (Biologia, 2024)

Potential of different strategies to increase intramuscular fat deposition in sheep: A meta-analysis study - Rodrigo de Nazaré Santos Torres; Caren Paludo Ghedini; Luis Artur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Jon Patrick Schoonmaker; Marco Tulio Costa Almeida; Ciniro Costa; Otavio Rodrigues Machado Neto (Small Ruminant Research, 2024)

Behavior of sows exposed to auditory enrichment in mixed or collective housing systems - Janaína Palermo Mendes; Fabiana Ribeiro Caldara; Maria Fernanda de Castro Burbarelli; Jean Kaique Valentim; Daniella Ferreira de Brito Mandu; Rodrigo Garofallo Garcia; Ibiara Correia de Lima Almeida Paz; Agnes Markiy Odakura; Marconi Italo Lourenço da Silva (Journal of Veterinary Behavior, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Polyethylene terephthalate (PET) as a recycled raw material for particleboards produced from pinus wood and biopolymer resin - Pedro Henrique da Silva Cazella; Matheus Viana de Souza; Felipe Reis Rodrigues; Sergio Augusto Mello da Silva; Rodrigo Andraus Bispo; Victor Almeida De Araujo; André Luis Christoforo (Journal of Cleaner Production, 2024)

Functional and structural attributes of Brazilian tropical and subtropical forests and savannas - Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Renata Dias Françoso; Vinícius Andrade Maia; José Roberto Rodrigues Pinto; Pedro Higuchi; Ana Carolina Silva; Jamir Afonso do Prado Júnior; Camila Laís Farrapo; Eddie Lenza; Henrique Mews; Helena L. Lemos Rocha; et al. (Forest Ecology and Management, 2024)

Dietary effect of multi-strain prebiotics and probiotics on growth, hemato-biochemical parameters, intestinal histomorphometry, and resistance to hypoxia in juvenile tambaqui (Colossoma macropomum) - Rafael José Furtado Souza; Edilson Rodrigues Matos; Aldry Lorran da Silva Souza; Paola Fabiana Fazzi-Gomes; Nuno Filipe Alves Correia de Melo; Marco Shizuo Owatari; Glauber David Almeida Palheta; Rodrigo Takata; Fabio Carneiro Sterzelecki (Veterinary Research Communications, 2024)

In vitro culture of Rio Grande cherry (Eugenia involucrata DC.) - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Rodrigo Rocha Latado; Sônia Maria De Stefano Piedade; Francisco de Assis Alves Mourão Filho (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Revisiting the shikimate pathway and highlighting their enzyme inhibitors - Aline Marengoni Almeida; Rogério Marchiosi; Josielle Abrahão; Rodrigo Polimeni Constantin; Wanderley Dantas dos Santos; Osvaldo Ferrarese-Filho (Phytochemistry Reviews, 2024)

Root-shoot ratio and SOD activity are associated with the sensitivity of common bean seedlings to NaCl salinization - Marina García; Grisaly García; Rodrigo Parola; Naga Raju Maddela; Iris Pérez-Almeida; Felipe R. Garcés-Fiallos (Rhizosphere, 2024)

Genetic association between fat-to-protein ratio and traits of economic interest in early lactation Holstein cows in Brazil - Denyus Augusto de Oliveira Padilha; Amauri Felipe Evangelista; Altair Antônio Valloto; Lenira El Faro Zadra; Rodrigo de Almeida; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Tropical Animal Health and Production, 2024)

Association of rainfall pattern with the disappearance of mineral mixtures fed cattle managed on tropical pastures - Zey Welington Gomes de Souza; Manoel Gustavo Paranhos da Silva; Andrei Pereira Neves; Thiago Luís Alves Campos de Araújo; Nickson Milton Correa Siqueira; Wallyson Almeida Amaral; Denise Baptaglin Montagner; Luís Carlos Vinhas Ítavo; Valter Bumbieris Júnior; Bruno Marson; Márcio de Nadai Bonin; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2024)

Environmental vulnerability index in Dipteryx alata: influence of abiotic stresses on central processes of plant physiology and metabolism - Leticia Ferreira Sousa; Paulo Eduardo Menezes-Silva; Priscila Ferreira Batista; Ana Paula Silva Alves; Maria Clara de Andrade PereiraSilva; Sabrina Emanuella da Silva Almeida; Rauander Douglas Ferreira Barros Alves; Lucas Loram Lourenço; Layara Alexandre Bessa; Adinan Alves da Silva; Alan Carlos Costa; Anderson Rodrigo da Silva; et al. (Acta Physiologiae Plantarum, 2024)

New curcumin-loaded nanocapsules as a therapeutic alternative in an amnesia model - Karline da Costa Rodrigues; Manoel Rodrigues da Silva Neto; Victor dos Santos Barboza; Sandra Elisa Hass; Rodrigo de Almeida Vaucher; Janice Luehring Giongo; Ricardo Frederico Schumacher; Ethel Antunes Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2024)

Somatic embryogenesis in Euterpe edulis Martius is improved by wounding, explant orientation, and suspension culture - Tamyris de Mello; Tatiane Dulcineia Silva; Tadeu Ériton Caliman Zanardo; Francine Alves Nogueira de Almeida; Luciano Bestete Oliveira; Clovis Eduardo Nunes Hegedus; Breno Benvindo dos Anjos; Edilson Romais Schmildt; Adésio Ferreira; Márcia Flores da Silva Ferreira; José Carlos Lopes; Glória Maria de Farias Viégas Aquije; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Growth, survival, and myogenic gene expression in the post-larvae of Colossoma macropomum provisioned with Artemia nauplii - Debora Sayumi Doami Melo; André Luiz Alves de Sá; Sávio Lucas de Matos Guerreiro; Joane Natividade; Paola Fabiana Fazzi Gomes; Rodrigo Takata; Ednaldo da Silva Filho; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; Fabio Carneiro Sterzelecki; Igor Hamoy (Fish Physiology and Biochemistry, 2024)

Characterization of ESBL/AmpC-producing extraintestinal Escherichia coli (ExPEC) in dogs treated at a veterinary hospital in Brazil - Brendhal Almeida Silva; Victor Santos do Amarante; Rafael Gariglio Clark Xavier; Salene Angelini Colombo; Tales Fernando da Silva; Bertram Brenig; Flavia Figueira Aburjaile; Vasco Ariston de Carvalho Azevedo; Rodrigo Otávio Silveira Silva (Research in Veterinary Science, 2024)

Long-term heat acclimation training in mice: Similar metabolic and running performance adaptations despite a lower absolute intensity than training at temperate conditions - Gustavo de Oliveira Zanetti; Pedro William Martins Pessoa; Tales Sambrano Vieira; Rodrigo de Almeida Garcia; Nicolas Henrique Santos Barbosa; Rosa Maria Esteves Arantes; Isis do Carmo Kettelhut; Luiz Carlos C. Navegantes; Samuel Penna Wanner; Danusa Dias Soares; Dawit Albieiro Pinheiro Gonçalves (Journal of Thermal Biology, 2024)

Gliding arc plasma jet for inhibiting mycotoxin production and apple brown rot by Alternaria alternata - Viviane Lopes Pereira; Elem Tamirys dos Santos Caramês; Naara Aparecida Almeida; William Chiappim; Rodrigo Sávio Pessoa; Gilberto Petraconi Filho; Liliana de Oliveira Rocha (Food Control, 2024)

Strategies of virginiamycin supplementation in the postweaning phase on growth performance and carcass quality of beef cattle - Rodrigo da Costa Gomes; Gilberto Romeiro de Oliveira Menezes; Ricardo Favero; Ricardo Kazama; Georg Altrak; Ivone Yurika Mizubuti; Marina de Nadai Bonin Gomes; Gelson Luis Dias Feijó; Denise Baptaglin Montagner; Thiago Luís Alves Campos de Araújo; Dorgival Morais de Lima Júnior; Roberto Augusto de Almeida Torres Júnior; et al. (Tropical Animal Health and Production, 2024)

The impact of fast-growing eucalypt plantations on C emissions in tropical soil: effect of belowground and aboveground C inputs - Rafael da Silva Teixeira; Daniela Cristina Costa; Valéria Santos Cavalcante; Ricardo Cardoso Fialho; Ana Paula Mendes Teixeira; Rodrigo Nogueira de Sousa; Aline de Almeida Vasconcelos; Ivo Ribeiro da Silva (Environmental Monitoring and Assessment, 2024)

Environmental monitoring of SARS-CoV-2 in the metropolitan area of Porto Alegre, Rio Grande do Sul (RS), Brazil - Leticia Batista Dutra; Janaína Francieli Stein; Bruna Seixas da Rocha; Andresa Berger; Beatriz Andrade de Souza; Bruno Aschidamini Prandi; Arthur Tonietto Mangini; André Jarenkow; Aline Alves Scarpellini Campos; Fernando Mainardi Fan; Maria Cristina de Almeida Silva; Katia Helena Lipp-Nissinen; et al. (Environmental Science and Pollution Research, 2023)
Since starts the coronavirus disease 2019 (COVID-19) pandemic identified the presence of genomic fragments of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in various environmental matrices: domestic sewage, surface waters, and contaminated freshwater. Environmental monitoring of SARS-CoV-2 is a tool for evaluating trend curves over the months, compared to several clinical cases of the disease. The objective of this study was to monitor the SARS-CoV-2 in environmental samples collected in different sites in a metropolitan area of Porto Alegre, Southern Brazil. During 10 months from 2020 to 2021, 300 samples were collected weekly and biweekly from nine points located in 3 cities: one point from a wastewater treatment plant (WWTP) in São Leopoldo (fortnightly collection), two points in Dilúvio Stream in Porto Alegre (fortnightly collection), two points in Pampa and Luiz Rau Streams (weekly collection), and two points in public fountains (fortnightly collection) in Novo Hamburgo. After collection, samples were concentrated by ultracentrifugation, and viral nucleic acids were extracted using MagMax® Core Nucleic Acid Purifications kits and submitted to RT-qPCR, using E, N1, and N2 gene targets of SARS-CoV-2. Only 7% (3/41) samples from public fountains were positive, with a mean viral load (VL) of SARS-CoV-2 RNA of 5.02 × 10 1 gc/l (2.41~8.59 × 10 1 gc/l), while the streams had average VL of 7.43 × 10 5 gc/l (Pampa), 7.06 × 10 5 gc/l (Luiz Rau), 2.01 × 10 5 gc/l (Dilúvio), and 4.46 × 10 5 cg/l (WWTP). The results showed varying levels of viral presence in different sample types, with a demonstrated correlation between environmental viral load and clinical COVID-19 cases. These findings contribute to understanding virus persistence and transmission pathways in the environment. Continuous monitoring, especially in less developed regions, is crucial for early detection of vaccine resistance, new variants, and potential COVID-19 resurgence.

Do tides equally influence the reproductive cycle of two symbiotic estuarine shrimp? - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Kombucha based on unconventional parts of the Hibiscus sabdariffa L.: Microbiological, physico-chemical, antioxidant activity, cytotoxicity and sensorial characteristics - Gislane Romano Mendonça; Rodrigo Anacleto Pinto; Érika Almeida Praxedes; Virgínia Kelly Gonçalves Abreu; Richard Pereira Dutra; Alexsandra Fernandes Pereira; Tatiana de Oliveira Lemos; Aramys Silva dos Reis; Ana Lúcia Fernandes Pereira (International Journal of Gastronomy and Food Science, 2023)

Short communication: Impact of corn grain particle size on production performance of lactating dairy cows - Isabela Fonseca Carrari; Milaine Poczynek; Aline Milani Fillus; Fernando Solano Baptista; Leopoldo Bras Los; Luiz Felipe Ferraretto; Alex Maiorka; Rodrigo de Almeida (Tropical Animal Health and Production, 2023)

Red Fluorescent Protein Variant with a Dual-Peak Emission of Fluorescence - Natalia Ossa-Hernández; Luis Fernando Marins; Rodrigo Volcan Almeida; Daniela Volcan Almeida (Marine Biotechnology, 2023)

Endophytic colonization of five Trichoderma species and their effects on growth of a Eucalyptus hybrid - Jéssica Bezerra Bandeira; Jovielly Neves Rodrigues; Rodrigo Silva de Oliveira; Ismael Oliveira Pinto; Aloísio Freitas Chagas-Júnior; Vitor L. Nascimento; Maíra Ignacio Sarmento; Cristiano Bueno de Moraes; Renato Almeida Sarmento (Brazilian Journal of Microbiology, 2023)

Identified senescence endotypes in aged cartilage are reflected in the blood metabolome - Ilja Boone; Margo Tuerlings; Rodrigo Coutinho de Almeida; Johannes Lehmann; Yolande Ramos; Rob Nelissen; Eline Slagboom; Peter de Keizer; Ingrid Meulenbelt (GeroScience, 2023)
Heterogeneous accumulation of senescent cells expressing the senescence-associated secretory phenotype (SASP) affects tissue homeostasis which leads to diseases, such as osteoarthritis (OA). In this study, we set out to characterize heterogeneity of cellular senescence within aged articular cartilage and explored the presence of corresponding metabolic profiles in blood that could function as representative biomarkers. Hereto, we set out to perform cluster analyses, using a gene-set of 131 senescence genes ( N = 57) in a previously established RNA sequencing dataset of aged articular cartilage and a generated metabolic dataset in overlapping blood samples. Using unsupervised hierarchical clustering and pathway analysis, we identified two robust cellular senescent endotypes. Endotype-1 was enriched for cell proliferating pathways, expressing forkhead box protein O4 ( FOXO4) , RB transcriptional corepressor like 2 ( RBL2) , and cyclin-dependent kinase inhibitor 1B ( CDKN1B) ; the FOXO mediated cell cycle was identified as possible target for endotype-1 patients. Endotype-2 showed enriched inflammation-associated pathways, expressed by interleukin 6 ( IL6) , matrix metallopeptidase (MMP)1/3 , and vascular endothelial growth factor (VEGF) C and SASP pathways were identified as possible targets for endotype-2 patients. Notably, plasma-based metabolic profiles in overlapping blood samples ( N = 21) showed two corresponding metabolic clusters in blood. These non-invasive metabolic profiles could function as biomarkers for patient-tailored targeting of senescence in OA.

Tracking new insights into antifungal and anti-mycotoxigenic properties of a biofilm forming Pediococcus pentosaceus strain isolated from grain silage - Carlos M.N. Mendonça; Rodrigo C. Oliveira; Lucas J.L. Pizauro; Wellison A. Pereira; Kahlile Abboud; Sonia Almeida; Ii-Sei Watanabe; Alessandro M. Varani; José M. Domínguez; Benedito Correa; Koen Venema; Pamela O.S. Azevedo; et al. (International Journal of Food Microbiology, 2023)

Chemical composition, antibacterial and cytotoxic activities of essential oil obtained from aerial parts of Aeschynomene denticulata Rudd - Rodrigo Elísio de Sá; Gisele Santos Araújo; Fabrício dos Santos Machado; Dakson Douglas Araújo; Raí Emanuel da Silva; Rodrigo Ferreira Santiago; Lorena Tuane Gomes de Almeida; José Delano Barreto Marinho Filho; Alyne Rodrigues de Araújo; Mariana Helena Chaves; Ana Jérsia Araújo (Biocatalysis and Agricultural Biotechnology, 2023)

Optimization of plastic polymers for shellfish aquaculture infrastructures: in situ antifouling performance assessment - Vânia Freitas; Odete Gonçalves; Marina Dolbeth; Sandra Ramos; João Morais; Rodrigo O. de A. Ozorio; Irene Martins; Joana R. Almeida (Frontiers in Marine Science, 2023)
Biofouling poses a significant challenge to bivalve aquaculture affecting both the target culture and/or the immersed infrastructure. In suspended bivalve cultures (e.g., oysters and scallops), biofouling accumulation leads to additional labor demands and increased costs for the maintenance of underwater structures. Given that the inherent properties of materials used in farming infrastructure influence the formation of fouling communities, evaluating how these materials perform under diverse environmental conditions can help the industry select the most effective materials for preventing or minimizing biofouling growth. This study evaluates the impact of aquaculture material and environmental conditions on biofouling, focusing on two commonly used plastic polymers in marine aquaculture: polyamide (PA) and high-density polyethylene (PE). Both untreated and color-additive treated polymers were tested for their response to fouling development. Performance was gauged by total fouling wet weight and the extent of fouling-induced mesh occlusion. Experimental panels were deployed for 4 months (from May to September 2021) in estuarine (oyster farm) and marine (port) environments on the northern coast of Portugal. The marine sites exhibited greater fouling species diversity, while higher biofouling loads were found in the subtidal estuarine area. Within 3 months, complete mesh occlusion occurred mainly due to colonial hydroids ( Obelia dichotoma ) in the subtidal site. In contrast, panels deployed in the intertidal estuarine area had lower fouling biomass and mesh occlusion. Notably, significant differences between polymer types and treatments were only evident in the estuarine intertidal area, with long air exposure during low tide. White panels outperformed orange ones in fouling biomass, and PA panels outperformed PE panels in mesh occlusion. These differences were attributed to the settlement and growth of the acorn barnacle Austrominius modestus , known to favor dark-colored and less hydrophilic surfaces. Considering that oyster production in intertidal areas is one of the most important aquaculture industries globally, these findings offer valuable insights into material selection and characteristics that can mitigate fouling loads and their associated impacts. These results could also be relevant for other forms of bivalve aquaculture where infrastructure-related biofouling presents a challenge.

Herbicides may threaten advances in biological control of diseases and pests - Rodrigo Almeida Pinheiro; Tayna Sousa Duque; Gabriela Madureira Barroso; Marcus Alvarenga Soares; Cassia Michelle Cabral; José Cola Zanuncio; José Barbosa dos Santos (Environmental Science and Pollution Research, 2023)

Placental scaffolds as a potential biological platform for embryonic stem cells differentiation into hepatic-like cells lineage: A pilot study - Rodrigo da Silva Nunes Barreto; Leandro Norberto da Silva Júnior; Gustavo Henrique Doná Rodrigues Almeida; Bianca de Oliveira Horvath-Pereira; Thamires Santos da Silva; Joaquim Mansano Garcia; Lawrence Charles Smith; Ana Claudia Oliveira Carreira; Maria Angelica Miglino (Tissue and Cell, 2023)

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

Control of basin-scale accommodation zones on syn-rift Aptian lacustrine carbonate reservoirs. Implications for reservoir quality estimates of Brazilian pre-salt - Pedro Henrique Silvany Sales; Mario Neto Cavalcanti de Araujo; Julio Cesar Horta de Almeida; Rodrigo Brandao Bunevich (Marine and Petroleum Geology, 2023)

Heating setpoint recommendation strategy for thermal comfort and energy consumption optimization - Rodrigo Almeida; Petia Georgieva; Nelson Martins (Energy and Buildings, 2023)

Estimation of genetic parameters for the tick and hemoparasite burden in Angus cattle - Gabriela David; Cherlynn Daniela da Silva Arce; Francisco Ribeiro de Araujo Neto; Lúcia Galvão de Albuquerque; Rodrigo Giglioti; Cíntia Hiromi Okino; Luciana Correia de Almeida Regitano; Márcia Cristina de Sena Oliveira; Henrique Nunes de Oliveira (Tropical Animal Health and Production, 2023)

Chemosystematics micromolecular evolutionary trends relevant to the Urticaceae family - Jéssica da Silva Maciel; Carolina Chaves Ramos; Adriana Lima de Sousa; Cibele Maria Stivanin de Almeida; Rodrigo Barbosa Braga Feitoza; Helena Regina Pinto Lima; Rodrigo Rodrigues de Oliveira (Plant Systematics and Evolution, 2023)

Application of Machine Learning Techniques to the Maritime Industry - Miguel Ángel Gómez Ruiz; Iván Martín de Almeida; Rodrigo Pérez Fernández (Journal of Marine Science and Engineering, 2023)
The maritime industry is displaying notable interest in the adoption of cutting-edge technologies within the scope of Industry 4.0, aiming to digitalize both companies and processes. At the core of data science lies machine learning, which serves as the focal point of this article. This study seeks to accomplish two main objectives: firstly, an exploration of various machine learning algorithms, and subsequently, the application of these techniques to analyze predictions within the propulsion system of a 9500 TEU container ship. The outcomes of the study reveal that utilizing distinct machine learning algorithms for predicting braking performance yields a lower mean square error (MSE) when compared to the discrepancy introduced by the J. Mau formula, as evident in the container ship database. The selection of propulsion engines was based on predictions for a 9500 TEU container ship. Similarly, promising outcomes were achieved in predicting propeller diameter in comparison to conventional methods. Thus, these predictions can also effectively guide the appropriate choice of propeller diameter.

Long exposure to a mixture of endocrine disruptors prediposes the ventral prostate of rats to preneoplastic lesions - Thaina Cavalleri Sousa; Letícia Pereira de Souza; Maria Luiza Silva Ricardo; Andreia Yuri Yoshigae; Karianne Delalibera Hinokuma; Ana Beatriz Ratto Gorzoni; Ariana Musa de Aquino; Wellerson Rodrigo Scarano; Anthony César de Sousa Castillho; Maria Eduarda Almeida Tavares; Alice Santos Cruz Veras; Giovana Rampazzo Teixeira; et al. (Environmental Science and Pollution Research, 2023)

Hydroclimatic influence on the trophic ecology of Atlantic goliath grouper juveniles (Epinephelus itajara) in a tropical estuary using non-lethal methodologies - Mario V. Condini; Alexandre M. Garcia; Rodrigo F. Bastos; Sabrina R. Vollrath; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Maurício Hostim-Silva (Marine Environmental Research, 2023)

Effects of acephate and glyphosate-based agrochemicals on the survival and flight of Plebeia lucii Moure, 2004 (Apidae: Meliponini) - Lívia Maria Negrini Ferreira; Michael Hrncir; Danilo Vieira de Almeida; Rodrigo Cupertino Bernardes; Maria Augusta Pereira Lima (Ecotoxicology, 2023)

Polyurethane foams incorporated with different fillers to remove SARS-CoV-2 from water - Thays França Afonso; Carolina Faccio Demarco; Guilherme Pereira Schoeler; Janice Luehring Giongo; Rodrigo de Almeida Vaucher; Tito Roberto Sant'Anna Cadaval; Simone Pieniz; Rafael de Avila Delucis; Robson Andreazza (Journal of Water Process Engineering, 2023)

The science we need for the beaches we want: frontiers of the flourishing Brazilian ecological sandy beach research - Guilherme Nascimento Corte; Yasmina Shah Esmaeili; Tatiana Fabricio Maria; Leonardo Lopes Costa; Gustavo Mattos; Helio Herminio Checon; Nicole Malinconico; Paulo Cesar Paiva; Paula Debiasi; Tatiana Cabrini; Victor Corrêa Seixas; Eduardo Bulhões; et al. (Frontiers in Marine Science, 2023)

Vaginal temperature modeling in Holstein cows and cluster analysis by the cophenetic correlation coefficient - Marcos Vinícius da Silva; Héliton Pandorfi; Maria Simone Mendes Peixoto; José Antonio Delfino Barbosa Filho; Gledson Luiz Pontes de Almeida; Iran José Oliveira da Silva; Kenio Patrício Lima de Oliveira; Vinícius de Sena Sales Viana; José Francisco de Oliveira-Júnior; Cristiane Guiselini; Gabriel Thales Barboza Marinho; Marcio Mesquita; et al. (Journal of Thermal Biology, 2023)

Metarhizium anisopliae E6 secretome reveals molecular players in host specificity and toxicity linked to cattle tick infection - Laura Rascovetzki Saciloto-de-Oliveira; Leonardo Broetto; Camila Innocente Alves; Rafael Lopes da Rosa; Yohana Porto Calegari Alves; Rodrigo Campos da Silva; Markus Berger; Alexandre José Macedo; Pedro Ferrari Dalberto; Cristiano Valim Bizarro; Jorge Almeida Guimarães; John R. Yates; et al. (Fungal Biology, 2023)

Nitric oxide-loaded nano- and microparticle platforms serving as potential new antifungal therapeutics - Sichen Liu; Daniel Zamith-Miranda; Rodrigo Almeida-Paes; Leandro Buffoni Roque da Silva; Parimala Nacharaju; Joshua D. Nosanchuk (Fungal Biology, 2023)

Stainless steel and titanium alloys coated with sulfated chitosan to improve hemocompatibility properties - Sandy Danielle Lucindo Gomes; Maria Rosiene Antunes Arcanjo; Francisca Raysse Mesquita Silva; Luzia Kalyne Almeida Moreira Leal; Ana Paula Rosifini Alves Claro; Ketul Popat; Rodrigo Silveira Vieira (In vitro models, 2023)

Barley systemic bioelectrical changes detect pathogenic infection days before the first disease symptoms - Francine Zaiosc Simmi; Leandro José Dallagnol; Rodrigo Oliveira Almeida; Keilor da Rosa Dorneles; Gustavo Maia Souza (Computers and Electronics in Agriculture, 2023)

Imputation accuracy for genomic selection using embryo biopsy samples in Gir - Clara Slade Oliveira; Marcos Vinicius Gualberto Barbosa da Silva; Carolina Capobiango Quintão; Pamela Itajara Otto; Rodrigo Vitorio Alonso; Luiz Fernando Feres; João Claudio do Carmo Panetto; Marco Antonio Machado; Luiz Sergio de Almeida Camargo (Reproductive Biology, 2023)

Use of prostaglandin E1 analog (misoprostol) to aid cervical dilation in birth induction (a case report) - Odilon Marquez Oliveira; Gabrielle Bueno de Almeida Goncalves Amorim; Rodrigo Arruda Oliveira; Eunice Oba (Journal of Equine Veterinary Science, 2023)

Effects of molasses supplementation on animal performance and carcass parameters of beef cattle: a meta-analysis - Rodrigo de Nazaré Santos Torres; João Pedro Amaral Bertoco; Maria Carolina Gonçalves de Arruda; Larissa de Melo Coelho; Josimari Regina Paschoaloto; Otavio Rodrigues Machado Neto; Jane Maria Bertocco Ezequiel; Marco Túlio Costa Almeida; Luis Artur Loyola Chardulo; Welder Angelo Baldassini (Tropical Animal Health and Production, 2023)

Heat-resistant and biofilm-forming Escherichia coli in pasteurized milk from Brazil - Maxsueli Aparecida Moura Machado; Vinicius Silva Castro; Adelino da Cunha-Neto; Deyse Christina Vallim; Rodrigo de Castro Lisbôa Pereira; Jaqueline Oliveira dos Reis; Patrícia Veiga de Almeida; Diego Galvan; Carlos Adam Conte-Junior; Eduardo Eustáquio de Souza Figueiredo (Brazilian Journal of Microbiology, 2023)

A review of 121 years of studies on the freshwater zooplankton of Brazil - Maria Stela Maioli Castilho-Noll; Gilmar Perbiche-Neves; Natan Guilherme dos Santos; Leilane Talita Fatoreto Schwind; Fernando Miranda Lansac-Tôha; Alan Cleber Santos da Silva; Bianca Ramos de Meira; Ciro Yoshio Joko; Cláudio Simões de Morais-Júnior; Edissa Emi Cortez Silva; Eneida Maria Eskinazi-Sant'Anna; Felipe Rafael Oliveira; et al. (Limnologica, 2023)

Grain-cropping suitability for evaluating the agricultural land use change in Brazil - José Lucas Safanelli; Rogério de Souza Nóia Júnior; Pedro Alves Quilici Coutinho; Marcela Almeida de Araujo; Arthur Nicolaus Fendrich; Rodnei Rizzo; Ana Letícia Sbitkowski Chamma; Paulo André Tavares; Alberto Giaroli de Oliveira Pereira Barretto; Rodrigo Fernando Maule; Klaus Reichardt; Gerd Sparovek; et al. (Applied Geography, 2023)

Organic fertilization and mycorrhization increase copper phytoremediation by Canavalia ensiformis in a sandy soil - Tauiris Santos Rangel; Natielo Almeida Santana; Rodrigo Josemar Seminoti Jacques; Rodrigo Ferraz Ramos; Douglas Leandro Scheid; Ezequiel Koppe; Luciane Almeri Tabaldi; Andressa de Oliveira Silveira (Environmental Science and Pollution Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Adipose and amnion-derived mesenchymal stem cells: Extracellular vesicles characterization and implication for reproductive biotechnology - Rodrigo Ferreira Scassiotti; Meline de Paula Coutinho; Sarah Ingrid Pinto Santos; Priscilla Avelino Ferreira Pinto; Matheus Ferreira de Almeida; Rafael Garcia Karam; Paola Maria da Silva Rosa; Daniele dos Santos Martins; Juliano Coelho da Silveira; Carlos Eduardo Ambrósio (Theriogenology, 2023)

Seafood consumers engagement in reducing environmental impacts from packaging - Cheila Almeida; Jara Laso; David Baptista de Sousa; Ronan Cooney; Paula Quinteiro; Neil Rowan; Ana Cláudia Dias; Eoghan Clifford; Rodrigo G. Reboredo; María Margallo; Maria Leonor Nunes; António Marques (Science of The Total Environment, 2023)

Potential of nutritional strategies to reduce enteric methane emission in feedlot sheep: A meta-analysis and multivariate analysis - Rodrigo de Nazaré Santos Torres; Larissa de Melo Coelho; Caren Paludo Ghedini; Otavio Rodrigues Machado Neto; Luis Artur Loyola Chardulo; Juliana Akamine Torrecilhas; Roberta de Lima Valença; Welder Angelo Baldassini; Marco Tulio Costa Almeida (Small Ruminant Research, 2023)

Genomic and physiological characterization of Novosphingobium terrae sp. nov., an alphaproteobacterium isolated from Cerrado soil containing a mega-sized chromid - Aline Belmok; Felipe Marques de Almeida; Rodrigo Theodoro Rocha; Carla Simone Vizzotto; Marcos Rogério Tótola; Marcelo Henrique Soller Ramada; Ricardo Henrique Krüger; Cynthia Maria Kyaw; Georgios J. Pappas (Brazilian Journal of Microbiology, 2023)

Tolerance in rice genotypes to the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo de S. Almeida; Anderson Rodrigo da Silva; Flávio G. de Jesus; José Alexandre de F. Barrigossi (Biologia, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

On Monitoring Mahanarva fimbriolata Stål (Hemiptera: Cercopidae) in Sugarcane Fertirrigated with Vinasse - Anderson Rodrigo Da Silva; Itamar José Tavares Filho; Flávio Gonçalves de Jesus; André Cirilo de Sousa Almeida (Sugar Tech, 2023)

Bedellia somnulentella (Lepidoptera: Bedelliidae): new hosts of the genus Ipomoea (Convolvulaceae) in Brazil - Maria Jéssica dos Santos Cabral; Ronnie Von dos Santos Veloso; Sebastião Lourenço de Assis Júnior; José Barbosa dos Santos; Germano Leão Demolin Leite; José Cola Zanuncio; Rodrigo Almeida Pinheiro; Marcus Alvarenga Soares (Journal of Plant Diseases and Protection, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Increased soybean tolerance to high-temperature through biostimulant based on Ascophyllum nodosum (L.) seaweed extract - Rodrigo Alberto Repke; Dayane Mércia Ribeiro Silva; Jania Claudia Camilo dos Santos; Marcelo de Almeida Silva (Journal of Applied Phycology, 2022)

Fipronil exposure compromises respiration and damages the Malpighian tubules of the stingless bee Partamona helleri Friese (Hymenoptera: Apidae) - Cliver Fernandes Farder-Gomes; Abraão Almeida Santos; Kenner Morais Fernandes; Rodrigo Cupertino Bernardes; Gustavo Ferreira Martins; José Eduardo Serrão (Environmental Science and Pollution Research, 2022)

Silicon amendment induces resistance in rice to Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo S. Almeida; Anderson Rodrigo da Silva; Michael J. Stout; Flávio G. de Jesus; José Alexandre F. Barrigossi (Arthropod-Plant Interactions, 2022)

Taxonomic and functional diversity patterns of stream fish assemblages from Brazilian Atlantic Rain Forest - Mauricio Cetra; Lucas Alejandro Garibaldi; Fabrício Barreto Teresa; Alexandre Peressin; Bruna Botti Cruz; Bruno José Gomes de Mello; Fernanda Ayumi Teshima; Rodrigo da Silva Almeida (Fisheries Management and Ecology, 2022)
Disentangling the hierarchical structure of river systems and multi‐scale environmental effects is essential for understanding freshwater fish community structure and function. We sampled 70 stream stretches to investigate how the taxonomic and functional composition and diversity of fish assemblages responded to the environment considering a hierarchical organisation of streams in three Brazilian watersheds (Upper Sorocaba, Upper Paranapanema and Upper Ribeira de Iguape). Functional diversity indicated that stream fish community function was independent of the watershed. The most critical environmental variable was substrate gradient. In streams with a consolidated substrate, equitability and functional dispersion were low due to invertivores occurring in this type of substrate. Our results highlight the importance of local environmental filters for shaping streams fish assemblages across different basins. This shaping was more evident when functional descriptors of assemblages were analysed, thereby reinforcing the importance of an approach based on traits as a tool to elucidate local community assembly processes at broader spatial scales.

Correction to: SARS-CoV-2 removal with a polyurethane foam composite - Guilherme Pereira Schoeler; Thays França Afonso; Carolina Faccio Demarco; Victor dos Santos Barboza; Tito Roberto Sant’anna Cadaval; Andrei Valerão Igansi; Marcos Alexandre Gelesky; Janice Luehring Giongo; Rodrigo de Almeida Vaucher; Rafael de Avila Delucis; Robson Andreazza (Environmental Science and Pollution Research, 2022)

The effect of hierarchical environmental structure and catchment-scale land cover on fish assemblage composition in streams from the Brazilian south-eastern rain forest - Rodrigo da Silva Almeida; Roberta de Oliveira Averna Valente; Mauricio Cetra (Hydrobiologia, 2022)

SARS-CoV-2 removal with a polyurethane foam composite - Guilherme Pereira Schoeler; Thays França Afonso; Carolina Faccio Demarco; Victor dos Santos Barboza; Tito Roberto Sant’anna Cadaval; Andrei Valerão Igansi; Marcos Alexandre Gelesky; Janice Luehring Giongo; Rodrigo de Almeida Vaucher; Rafael de Avila Delucis; Robson Andreazza (Environmental Science and Pollution Research, 2022)

Functional characterization of the pUceS8.3 promoter and its potential use for ectopic gene overexpression - Rodrigo Rocha Fragoso; Fabricio Barbosa Monteiro Arraes; Isabela Tristan Lourenço-Tessutti; Vívian Jesus Miranda; Marcos Fernando Basso; André Vinicius Júlio Ferreira; Antônio Américo Barbosa Viana; Camila Barrozo Jesus Lins; Philippe Castro Lins; Stéfanie Menezes Moura; João Aguiar Nogueira Batista; Maria Cristina Mattar Silva; et al. (Planta, 2022)

Ecological risk of imidacloprid on the Brazilian non-target freshwater organisms Chironomus sancticaroli and Poecilia reticulata - Lucas Gonçalves Queiroz; Caio César Achiles do Prado; Daniel Clemente Vieira Rêgo da Silva; Luiz Eduardo Thans Gomes; Rodrigo José Marassi; Éryka Costa Almeida; Ernani Pinto; Flávio Teixeira da Silva; Teresa Cristina Brazil de Paiva (Environmental Monitoring and Assessment, 2022)

Does the same refuge signify the same reproductive tactics? Comparing the mating systems of two symbiont alpheid shrimps (Crustacea: Decapoda) - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Marine Ecology, 2022)
Animal populations can present different mating tactics according to the number of mates males or females obtain. The limiting factors for copulation in symbiont crustaceans are the size, structural complexity, and density of refuge, in addition to predation risk outside their shelters. In this study, we aimed to investigate, comparatively, if the occupation of the same refuge leads to the same reproductive tactic in two symbiont species of alpheid shrimps. For this purpose, we described the population distribution of Alpheus estuariensis , a burrowing shrimp, and Salmoneus carvachoi , a tenant species, in an intertidal mudflat in Pernambuco, northeastern Brazil. Alpheus estuariensis experiences sexual dimorphism relative to body and cheliped size, where males present larger body sizes and allocate more resources to cheliped growth than females. However, both males and females presented positive allometric growth in chelipeds. In S. carvachoi , male‐phase individuals reach smaller body sizes than hermaphrodites. Male‐phase shrimps experience positive allometry in cheliped size, while hermaphrodites do not. Both species were found inhabiting burrows as sexual pairs more frequently than expected by chance. Paired females of A. estuariensis were found carrying embryos more frequently than solitary ones. We did not find a statistical difference between the frequency of single and paired ovigerous hermaphrodites in S. carvachoi . Our results indicate that A. estuariensis is social monogamous, while S. carvachoi is promiscuous. We argue that different biological and ecological aspects of these species could explain the distinct tactics adopted by them. Alpheus estuariensis digs its own refuge and is a much larger species, bearing a more robust cheliped than S. carvachoi . Thus, we argue that the burrowing species ( A. estuariensis ) should monopolize and defend their refuge, and S. carvachoi only takes advantage of this resource.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Anti-Sporothrix Antibody Detection in Domestic Cats as an Indicator of a Possible New Occurrence Area for Sporotrichosis in North Brazil - Andréa Reis Bernardes-Engemann; Marcos de Abreu Almeida; Ividy Bison; Vanessa Brito de Souza Rabello; Mariana Lucy Mesquita Ramos; Sandro Antonio Pereira; Rodrigo Almeida-Paes; Arthur Willian de Lima Brasil; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2022)

Unveiling the first steps of juvenile Atlantic goliath grouper Epinephelus itajara (Perciformes: Epinephelidae) in a tropical estuary at the southwestern Atlantic coast - Rodrigo Augusto Moreno-Santos; Mario Vinicius Condini; Lorena Lopes Almeida; Marcelo Soeth; Áthila Andrade Bertoncini; Mauricio Hostim-Silva (Marine Biology Research, 2022)

A Genetic Model of Epilepsy with a Partial Alzheimer’s Disease-Like Phenotype and Central Insulin Resistance - Suélen Santos Alves; Rui Milton Patrício da Silva Junior; Polianna Delfino-Pereira; Marilia Gabriella Alves Goulart Pereira; Israel Vasconcelos; Hanna Schwaemmle; Rodrigo Focosi Mazzei; Maiko Luiz Carlos; Enilza Maria Espreafico; Antônio Claudio Tedesco; Adriano Sebollela; Sebastião Sousa Almeida; et al. (Molecular Neurobiology, 2022)

Glioprotective Effects of Resveratrol Against BMAA-Induced Astroglial Dysfunctions - Filipe Renato Pereira Dias; Rômulo Rodrigo de Souza Almeida; Vanessa Sovrani; Natalie K. Thomaz; Carlos-Alberto Gonçalves; André Quincozes-Santos; Larissa Daniele Bobermin (Neurotoxicity Research, 2022)

Pyrolysis of Coconut Inflorescence Wastes: Production, Effects of Parameters, Characterization and Optimization of Phenolic-Rich Bio-Oil - Rodrigo Oliveira Farias; Pollyanna Vanessa Santos Lins; Rafaela Gabriel; Alson David Rodrigues Silva; Lívia Luísa Melo Carvalho; Lucas Meili; Allan Almeida Albuquerque; Sandra Helena Vieira Carvalho; João Inácio Soletti; Mozart Daltro Bispo (International Journal of Environmental Research, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Lipopolysaccharide Induces Gliotoxicity in Hippocampal Astrocytes from Aged Rats: Insights About the Glioprotective Roles of Resveratrol - Larissa Daniele Bobermin; Rômulo Rodrigo de Souza Almeida; Fernanda Becker Weber; Lara Scopel Medeiros; Lívia Medeiros; Angela T. S. Wyse; Carlos-Alberto Gonçalves; André Quincozes-Santos (Molecular Neurobiology, 2022)

Uniparental markers reveal new insights on subcontinental ancestry and sex-biased admixture in Brazil - Iriel A. Joerin-Luque; Danillo G. Augusto; Verónica Calonga-Solís; Rodrigo Coutinho de Almeida; Claudemira Vieira Gusmão Lopes; Maria Luiza Petzl-Erler; Marcia Holsbach Beltrame (Molecular Genetics and Genomics, 2022)

The Historical Burden of Sporotrichosis in Brazil: a Systematic Review of Cases Reported from 1907 to 2020 - Vanessa Brito Souza Rabello; Marcos Abreu Almeida; Andrea Reis Bernardes-Engemann; Rodrigo Almeida-Paes; Priscila Marques de Macedo; Rosely Maria Zancopé-Oliveira (Brazilian Journal of Microbiology, 2022)

Clostridioides difficile and multi-drug-resistant staphylococci in free-living rodents and marsupials in parks of Belo Horizonte, Brazil - Jordana Almeida Santana; Salene Angelini Colombo; Brendhal Almeida Silva; Amanda Nádia Diniz; Lara Ribeiro de Almeida; Carlos Augusto Oliveira Junior; Francisco Carlos Faria Lobato; Giliane de Souza Trindade; Adriano Pereira Paglia; Rodrigo Otávio Silveira Silva (Brazilian Journal of Microbiology, 2022)

Sporotrichosis After Tattooing Caused by Sporothrix brasiliensis - Vivian Fichman; Dayvison Francis Saraiva Freitas; Priscila Marques de Macedo; Antonio Carlos Francesconi do Valle; Fernando Almeida-Silva; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes; Maria Clara Gutierrez-Galhardo (Mycopathologia, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Benthic Cyanobacterial Diversity and Antagonistic Interactions in Abrolhos Bank: Allelopathy, Susceptibility to Herbivory, and Toxicity - Felipe de Vargas Ribeiro; Taiara Aguiar Caires; Marcela Alvarenga de Almeida Simões; Paulo Iiboshi Hargreaves; Livia Bonetti Villela; Giovana de Oliveira Fistarol; Alexandre Brauns Cazelgrandi; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Renato Crespo Pereira; Paulo Sergio Salomon (Frontiers in Marine Science, 2022)
Benthic cyanobacterial mats (BCMs) are conspicuous components of coral reef communities, where they play key ecological roles as primary producers among others. BCMs often bloom and might outcompete neighboring benthic organisms, including reef-building corals. We investigated the cyanobacterial species composition of three BCMs morphotypes from the marginal reef complex of Abrolhos Bank (Southeastern Brazil). Also, we assessed their allelopathic effects on coral zooxanthellae, their susceptibility to herbivory by fish, and their toxicity to brine shrimp nauplii. Morphology and 16S rDNA sequencing unveiled the cyanobacteria Moorena bouillonii , Okeania erythroflocculosa , Adonisia turfae , Leptolyngbya sp., and Halomicronema sp. as components of BCMs from Abrolhos. BCMs cell-free filtrates and extracts exerted an allelopathic effect by reducing the growth of the ex hospite Symbiodinium sp. in culture. BCMs-only treatments remained untouched in field susceptibility assays in contrast to macroalgae only and mixed BCMs-macroalgae treatments that had the macroalgae fully removed by reef fish. Crude aqueous extracts from BCMs were toxic to brine shrimps in acute assays. Besides unveiling the diversity of BCMs consortia in Abrolhos, our results cast some light on their allelopathy, antiherbivory, and toxicity properties. These antagonistic interactions might promote adverse cascading effects during benthic cyanobacteria blooms and in gradual shifts to BCMs-dominated states.

Contrasting continental patterns and drivers of taxonomic and functional turnover among fish assemblages across Brazilian reservoirs - Fernando Mayer Pelicice; Luciana da Silva Damasceno; Eveline de Almeida Ferreira; Weferson Júnio da Graça; Carlos Sérgio Agostinho; Rodrigo Fernandes (Hydrobiologia, 2022)

Antitumor effect of Cymbopogon densiflorus (Linneu) essential oil in bladder cancer cells - Gizele Lucia da Costa Pereira; Tamires Cunha Almeida; Janaina Brandão Seibert; Tatiane Roquete Amparo; Rodrigo Dian de Oliveira Aguiar Soares; Ivanildes Vasconcelos Rodrigues; Gustavo Henrique Bianco de Souza; Orlando David Henrique dos Santos; Glenda Nicioli da Silva (Natural Product Research, 2021)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Gliotoxicity and Glioprotection: the Dual Role of Glial Cells - André Quincozes-Santos; Camila Leite Santos; Rômulo Rodrigo de Souza Almeida; Amanda da Silva; Natalie K. Thomaz; Naithan Ludian Fernandes Costa; Fernanda Becker Weber; Izaviany Schmitz; Lara Scopel Medeiros; Lívia Medeiros; Bethina Segabinazzi Dotto; Filipe Renato Pereira Dias; et al. (Molecular Neurobiology, 2021)

Photocatalytic degradation of Novacron blue and Novacron yellow textile dyes by the TiO2/palygorskite nanocomposite - Mikaely Lizandra Moreira de Assis; Elmar Damasceno Junior; Janiele Mayara Ferreira de Almeida; Isabel do Nascimento Silva; Rodrigo Victor Barbosa; Lamara Maciel dos Santos; Elizete Faustino Dias; Nedja Suely Fernandes; Carlos Alberto Martinez-Huitle (Environmental Science and Pollution Research, 2021)

Eisenia andrei Behavioral and Antioxidative Responses to Excess of Copper in the Soil - Barbara Clasen; Talita Ferreira; Natielo Almeida Santana; Valéria Ortaça Portela; Vania L. Loro; Camila R. Murussi; Jossiele Leitemperger; Tadeu Luis Tiecher; Jorge Domínguez; Rodrigo Josemar Seminoti Jacques; Tamiris Rosso Storck; Zaida Inês Antoniolli (Water, Air, & Soil Pollution, 2021)

LT‐Brazil: A database of leaf traits across biomes and vegetation types in Brazil - Eduardo Mariano; Taciana F. Gomes; Silvia R. M. Lins; Adibe L. Abdalla‐Filho; Amin Soltangheisi; Maria G. S. Araújo; Rodrigo F. Almeida; Fernanda G. Augusto; Luiza P. Canisares; Siglea S. F. Chaves; Cristiane F. G. Costa; Thaís R. Diniz‐Reis; et al. (Global Ecology and Biogeography, 2021)
Motivation Leaf traits represent an important component of plant functional strategies, and those related to carbon fixation and nutrient acquisition form the leaf economics spectrum. However, observations of functional leaf traits are underrepresented in tropical regions in comparison with those in temperate areas. Brazil, a country with continental scale and vast biodiversity is a timely example, where many biomes are impacted by human activities and climate change. However, leaf traits relevant to understand vegetation responses to these impacts remain poorly quantified for many species found in the country. We compiled an extensive data set of four functional leaf traits for native woody species occurring in the Brazilian territory. In addition to trait observations, sampling dates and geo‐references were compiled and climatic parameters and soil properties of each sampling site were extracted from several databases. Main types of variables contained The LT‐Brazil data set contains 3,479, 1,216, 775 and 775 clean observations of leaf mass per area, leaf nitrogen (N) concentration per unit mass, leaf phosphorus (P) concentration per unit mass, and leaf N : P ratio, respectively, from native woody species, encompassing information of biome, vegetation, taxonomic data, geographical coordinates, climatic parameters, as well as soil properties. Spatial location and grain We compiled trait observations from 223 sites under native vegetation distributed in all main biomes (i.e., Amazônia, Caatinga, Cerrado, Mata Atlântica, Pampa and Pantanal) across the Brazilian territory. Time period and grain The data represent information published and/or sampled during the last 25 years. Major taxa and level of measurement Our compilation was focused on trait data observed for native woody species, excluding monocots, palm trees, herbs, and hemiparasitic plants. Thus, 108, 478 and 1,321 botanical families, genera and species were included, covering c . 9% of the woody angiosperm flora of Brazil. Software format Data are provided as comma‐separated value (.csv) files.

Can roughage: concentrate ratio affect the action of red propolis extract on sheep metabolism? - Yara America da Silva; Vitor Visintin Silva de Almeida; Aline Cardoso Oliveira; Rodrigo Souza Fonseca; Patrícia dos Santos; Julimar do Sacramento Ribeiro; Maria Josilaine Matos dos Santos Silva; Dorgival Morais de Lima Júnior (Tropical Animal Health and Production, 2021)

Exploring the bioactivity potential of Leonotis nepetifolia : phytochemical composition, antimicrobial and antileishmanial activities of extracts from different anatomical parts - Diego Pinto de Oliveira; Letícia de Almeida; Marcos José Marques; Roberta Ribeiro de Carvalho; Amanda Latércia Tranches Dias; Geraldo Alves da Silva; Rodrigo Maia de Pádua; Fernão Castro Braga; Marcelo Aparecido da Silva (Natural Product Research, 2021)

Reconstruction of Marine Commercial Landings for the Brazilian Industrial and Artisanal Fisheries From 1950 to 2015 - Kátia Meirelles Felizola Freire; Zafira da Silva de Almeida; José Raimundo Emanoel Trindade Amador; José Augusto Aragão; Ana Rosa da Rocha Araújo; Antônio Olinto Ávila-da-Silva; Bianca Bentes; Marcus Henrique Carneiro; Julien Chiquieri; Cezar Augusto Freire Fernandes; Marina Bezerra Figueiredo; Maurício Hostim-Silva; et al. (Frontiers in Marine Science, 2021)
Landing data are the most basic information used to manage fisheries, although they are often unavailable or incomplete. The objective of this work was to reconstruct the national database of marine commercial landings for the Brazilian industrial and artisanal fisheries, from 1950 to 2015. Total landings increased strongly from 1950 to mid-1980s and suffered sharp decline in the early 1990s, mainly associated to the collapse of sardine fisheries. After that, another period of increasing landings was observed, but at a much lower rate. Industrial landings always surpassed artisanal landings in Brazilian waters, except for the beginning of the time series, when many industrial fleets had not started yet, and in the early 2000s, when a change in the methodology for collecting landing statistics was implemented in the state of Pará leading to an overestimation of artisanal landings. Artisanal fisheries have been declining since 2005, which is worrisome due to the social impact it may have on local income and food security. Regional differences were also observed, with industrial landings being always higher than artisanal landings in southeastern-southern Brazil, while the opposite was true for the northern-northeastern regions. Higher landings were observed in the southeastern-southern regions when both artisanal and industrial fleets were combined. Sardine and demersal fishes were the main resources landed by industrial fishers. Artisanal fishers caught more species than their industrial counterpart, featuring Xiphopenaeus kroyeri , Cynoscion acoupa , and Ucides cordatus . Although the fishing of Epinephelus itajara was banned in Brazil, it continues to be landed. Yet, catches of this species and others under some threat status are still not properly registered, including: Carcharhinus longimanus , Galeorhinus galeus , Sphyrna lewini , Sphyrna mokarran , Pristis pectinata , and Pseudobatos horkelii . Fishing resources not identified in previous landing reconstruction efforts, such as sea urchins and sea cucumbers, have now been reported. The database presented here should be continuously updated and improved. It is of paramount importance to resume the collection of landing statistics, including information on fishing effort, to assess the relative impact of fisheries and environmental factors on the main Brazilian fishing stocks.

Disease Outbreak in a Keystone Grazer Population Brings Hope to the Recovery of Macroalgal Forests in a Barren Dominated Island - Francesca Gizzi; João Gama Monteiro; Rodrigo Silva; Susanne Schäfer; Nuno Castro; Silvia Almeida; Sahar Chebaane; Alejandro Bernal-Ibáñez; Filipe Henriques; Ignacio Gestoso; João Canning-Clode (Frontiers in Marine Science, 2021)
Macroalgal forests play a key role in shallow temperate rocky reefs worldwide, supporting communities with high productivity and providing several ecosystem services. Sea urchin grazing has been increasingly influencing spatial and temporal variation in algae distributions and it has become the main cause for the loss of these habitats in many coastal areas, causing a phase shift from macroalgae habitats to barren grounds. The low productive barrens often establish as alternative stable states and only a major reduction in sea urchin density can trigger the recovery of macroalgal forests. The present study aims to assess if the 2018 disease outbreak, responsible for a strong reduction in the sea urchin Diadema africanum densities in Madeira Island, was able to trigger a reverse shift from barren grounds into macroalgae-dominated state. By assessing the diversity and abundance of benthic sessile organisms, macroinvertebrates and fishes before, during and after that particular mass mortality event, we evaluate changes in benthic assemblages and relate them to variations in grazer and herbivore densities. Our results revealed a clear shift from barren state to a macroalgae habitat, with barrens characterized by bare substrate, sessile invertebrate and Crustose Coralline Algae (CCA) disappearing after the mortality event. Overall variations in benthic assemblages was best explained by four taxa (among grazers and herbivores species). However, it was the 2018 demise of D. africanum and its density reduction that most contributed to the reverse shift from a long stable barren state to a richer benthic assemblage with higher abundance of macroalgae. Despite this recent increase in macroalgae dominated habitats, their stability and persistence in Madeira Island is fragile, since it was triggered by an unpredictable disease outbreak and depends on how D. africanum populations will recover. With no control mechanisms, local urchin populations can easily reach the tipping point needed to promote a new shift into barren states. New conservation measures and active restoration are likely required to maintain and promote the local stability of macroalgal forests.

Production of Secreted Carbohydrates that Present Immunologic Similarities with the Cryptococcus Glucuronoxylomannan by Members of the Trichosporonaceae Family: A Comparative Study Among Species of Clinical Interest - Iara Bastos de Andrade; Marcos de Abreu Almeida; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Alessandra Leal da Silva Chaves; Susana Frases; Rosely Maria Zancopé-Oliveira; Fábio Brito-Santos; Rodrigo Almeida-Paes (Mycopathologia, 2021)

Impact of Cashew (Anacardium occidentale L.) by-Product on Composition and Metabolic Activity of Human Colonic Microbiota In Vitro Indicates Prebiotic Properties - Francisca Nayara Dantas Duarte Menezes; Érika Tayse da Cruz Almeida; Arthur Rodrigo da Silva Vieira; Jailane de Souza Aquino; Marcos dos Santos Lima; Marciane Magnani; Evandro Leite de Souza (Current Microbiology, 2021)

Decolorization and detoxification of different azo dyes by Phanerochaete chrysosporium ME-446 under submerged fermentation - Alana Pereira de Almeida; Andrew Macrae; Bernardo Dias Ribeiro; Rodrigo Pires do Nascimento (Brazilian Journal of Microbiology, 2021)

Comparative functional responses predict the predatory impact of the highly invasive fish Cichla kelberi - Thiago Lima Carvalho; Eveline de Almeida Ferreira; Fernando Mayer Pelicice; Rodrigo Fernandes (Hydrobiologia, 2021)

Artificial flooding changes soil chemistry and carbon dynamics in upland forests next to hydropower plant in Amazon basin - Guilherme Henrique Almeida Pereira; Vanessa Francieli Vital Silva; Rodrigo Camara; Vanessa Aparecida Fréo; Marcos Gervasio Pereira (Environment, Development and Sustainability, 2021)

Inferring ethylene temporal and spatial distribution in an apple orchard (Malus domestica Borkh): a pilot study for optimal sampling with a gas sensor - João Valente; Rodrigo Almeida; Lammert Kooistra (Horticulture, Environment, and Biotechnology, 2021)
Apples emit a volatile organic compounds during the ripening process named ethylene, which can be used to infer the optimal harvest time. Currently, the fruit ethylene emission is assessed in controlled facilities, thus laborious and expensive. This article pioneers the study of assessing ethylene emissions in uncontrolled environments. However, understanding how the ethylene spatial temporal dynamics in an open field, its still elusive. Therefore, this paper provides a model from an ( Malus domestica Borkh) apple orchard for simulation and analysis of ethylene behaviour. We demonstrate that the model is able to explain the ethylene emissions behaviour in an orchard field when subject to different wind speeds, directions and ripeness stages. Based on that we have investigated different sampling schemes—regular and random—for capturing the variability of ethylene in an orchard using an electrochemical gas sensor. These results show that a random sampling scheme performs 25% better than an equivalent regular-defined grid. Moreover, the measurements acquired locally in the rows tend to be 10% more reliable than in other locations from the orchard. Finally, the ethylene variability can be assessed with a confidence of 75% using 4 and 16 sampling points.

Centrifuge Modeling of Soft Soil Reinforced with Granular Columns - Fernando Saboya; Sérgio Tibana; Rodrigo Martins Reis; Thamara Fonte-Boa; Marcio de Souza Soares de Almeida; Maria Esther Soares Marques (Geotechnical and Geological Engineering, 2021)

Effects of stocking density on survival, growth and stress resistance of juvenile tambaqui (Colossoma macropomum) reared in a recirculating aquaculture system (RAS) - Walisson de Souza e Silva; Andre Lima Ferreira; Luanna do Carmo Neves; Nathália Soares Ferreira; Glauber David Almeida Palheta; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2021)

Bacteriological, cytological, and molecular investigation of Corynebacterium pseudotuberculosis, mycobacteria, and other bacteria in caseous lymphadenitis and healthy lymph nodes of slaughtered sheep - Thiago de Oliveira Zamprogna; Dayana Ribeiro; Vasco A.C. Azevedo; Gustavo Henrique Batista Lara; Rodrigo Garcia Motta; Rodrigo Costa da Silva; Amanda Keller Siqueira; Geraldo de Nardi Júnior; Fernando José Paganini Listoni; Lorrayne de Souza Araújo Martins; Aristeu Vieira da Silva; Fábio Vinícius Ramos Portilho; et al. (Brazilian Journal of Microbiology, 2021)

Canine sporotrichosis: polyphasic taxonomy and antifungal susceptibility profiles of Sporothrix species in an endemic area in Brazil - Jéssica Sepulveda Boechat; Sandro Antonio Pereira; Ana Caroline de Sá Machado; Paula Gonçalves Viana; Rodrigo Almeida-Paes; Rosely Maria Zancopé-Oliveira; Isabella Dib Ferreira Gremião; Manoel Marques Evangelista de Oliveira (Brazilian Journal of Microbiology, 2021)

Evolution of virulence-related phenotypes of Sporothrix brasiliensis isolates from patients with chronic sporotrichosis and acquired immunodeficiency syndrome - Ingrid Ludmila Rodrigues Cruz; Dayvison Francis Saraiva Freitas; Priscila Marques de Macedo; Maria Clara Gutierrez-Galhardo; Antonio Carlos Francesconi do Valle; Marcos de Abreu Almeida; Rowena Alves Coelho; Fábio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2021)

Sugarcane Harvesting Quality by Digital Image Processing - Guilherme De Moura Araújo; Fernando Ferreira Lima dos Santos; Samira Luns Hatum de Almeida; Rodrigo Nogueira Martins; Murilo Aparecido Voltarelli; Carla Segatto Strini Paixão; Francisco de Assis de Carvalho Pinto (Sugar Tech, 2021)

Methylglyoxal-Mediated Dopamine Depletion, Working Memory Deficit, and Depression-Like Behavior Are Prevented by a Dopamine/Noradrenaline Reuptake Inhibitor - Gudrian Ricardo Lopes de Almeida; Jozimar Carlos Szczepanik; Ingrid Selhorst; Ariana Ern Schmitz; Bárbara dos Santos; Maurício Peña Cunha; Isabella Aparecida Heinrich; Gabriela Cristina de Paula; Andreza Fabro De Bem; Rodrigo Bainy Leal; Alcir Luiz Dafre (Molecular Neurobiology, 2021)

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Nitrogen Fertilizer Recovery and Partitioning Related to Soybean Yield - Clovis Pierozan Junior; José Laércio Favarin; Bruno Cocco Lago; Rodrigo Estevam Munhoz de Almeida; Silas Maciel de Oliveira; Paulo Cesar Ocheuze Trivelin; Felipe Brendler Oliveira; Amanda Prado Gilabel (Journal of Soil Science and Plant Nutrition, 2020)

Wooden breast myopathy on broiler breast fillets affects quality and consumer preference - Andrey Sávio de Almeida Assunção; Rodrigo Garófallo Garcia; Claudia Marie Komiyama; Érika Rosendo de Sena Gandra; Jacqueline Rosa de Souza; Wellington dos Santos; Fabiana Ribeiro Caldara; Renata Aparecida Martins (Tropical Animal Health and Production, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: A role for mast cells and mast cell tryptase in driving neutrophil recruitment in LPS-induced lung inflammation via protease-activated receptor 2 in mice - Aline Dias de Almeida; Irismara Sousa Silva; Weslley Fernandes-Braga; Antônio Carlos Melo LimaFilho; Rodrigo Machado Florentino; Ayslan Barra; Luciana de Oliveira Andrade; M. Fátima Leite; Geovanni Dantas Cassali; André Klein (Inflammation Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Comparative Analysis of Putative Virulence-Associated Factors of Microsporum canis Isolates from Human and Animal Patients - Mariana Lucy Mesquita Ramos; Rowena Alves Coelho; Fabio Brito-Santos; Davson Guimarães; Mario Premazzi; Rosely Maria Zancopé-Oliveira; Sandro Antônio Pereira; Isabella Dib Ferreira Gremião; Rosane Orofino-Costa; Maria Helena Galdino Figueiredo-Carvalho; Rodrigo Almeida-Paes (Mycopathologia, 2020)

Population structure and adaptation of a bacterial pathogen in California grapevines - Mathieu Vanhove; Anne Sicard; Jeffery Ezennia; Nina Leviten; Rodrigo P.P. Almeida (Environmental Microbiology, 2020)
Summary Xylella fastidiosa subsp. fastidiosa causes Pierce's disease of grapevine (PD) and has been present in California for over a century. A singly introduced genotype spread across the state causing large outbreaks and damaging the grapevine industry. This study presents 122 X . fastidiosa subsp. fastidiosa genomes from symptomatic grapevines, and explores pathogen genetic diversity associated with PD in California. A total of 5218 single‐nucleotide polymorphisms (SNPs) were found in the dataset. Strong population genetic structure was found; isolates split into five genetic clusters divided into two lineages. The core/soft‐core genome constituted 41.2% of the total genome, emphasizing the high genetic variability of X . fastidiosa genomes. An ecological niche model was performed to estimate the environmental niche of the pathogen within California and to identify key climatic factors involved in dispersal. A landscape genomic approach was undertaken aiming to link local adaptation to climatic factors. A total of 18 non‐synonymous polymorphisms found to be under selective pressures were correlated with at least one environmental variable highlighting the role of temperature, precipitation and elevation on X . fastidiosa adaptation to grapevines in California. Finally, the contribution to virulence of three of the genes under positive selective pressure and of one recombinant gene was studied by reverse genetics.

Molecular identification and antifungal susceptibility testing of Pucciniomycotina red yeast clinical isolates from Rio de Janeiro, Brazil - Fabio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Jean Carlos Almeida de Oliveira; Raissa Vieira Monteiro; Alessandra Leal da Silva Chaves; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2020)

Stationary and non‐stationary detection of extreme precipitation events and trends of average precipitation from 1980 to 2010 in the Paraná River basin, Brazil - Ana Carolina Freitas Xavier; Anderson Paulo Rudke; Thais Fujita; Gabriel Constantino Blain; Marcos Vinicius Bueno de Morais; Daniela Sanches de Almeida; Sameh Adib Abou Rafee; Leila Droprinchinski Martins; Rodrigo Augusto Ferreira de Souza; Edimilson Dias de Freitas; Jorge Alberto Martins (International Journal of Climatology, 2020)
The main objective of this study was to investigate the trends on average and extreme events in time series of daily precipitation from 1980 to 2010 in the Paraná River basin, Brazil. The nonparametric Mann–Kendall test was applied to detect monotonic trend in the precipitation series. The occurrence of extreme values was analysed based on three generalized extreme values (GEV) models: Model 1 (stationary), Model 2 (non‐stationary for location parameter), and Model 3 (non‐stationary for location and scale parameters). The GEV parameters were estimated by the Generalized Maximum Likelihood method (GMLE) and for the non‐stationary models, the parameters were estimated as linear functions of time. To choose the most suitable model, the maximum likelihood ratio test ( D ) was used. From the results observed at the monthly scale, it was possible to infer that the months with the highest probability of an extreme weather event occurrence are February (climates Aw and Cfa), July (Cfa and Cfb), and October (Aw, Cfa, and Cfb). Approximately 90% of the 1,112 stations presented no trend regarding the GEV parameters. The non‐stationarity showed by other stations (Models 2 and 3) might be associated with several factors, such as the alteration of land use due to the north expansion of the agricultural border of the Paraná River basin.

Histoplasmosis Outbreaks in Brazil: Lessons to Learn About Preventing Exposure - Bernardo Tenório Guerra; Fernando Almeida-Silva; Rodrigo Almeida-Paes; Rossana Patrícia Basso; João Paulo Romualdo Alarcão Bernardes; Marcos Abreu Almeida; Lisandra Serra Damasceno; Melissa Orzechowski Xavier; Bodo Wanke; Rosely M. Zancopé-Oliveira; Marcus de Melo Teixeira (Mycopathologia, 2019)

Geospatial variation of physical attributes and sugarcane productivity in cohesive soils - Thiago Rodrigo Schossler; Bruno Campos Mantovanelli; Brivaldo Gomes de Almeida; Fernando José Freire; Manassés Mesquita da Silva; Ceres Duarte Guedes Cabral de Almeida; Maria Betânia Galvão dos Santos Freire (Precision Agriculture, 2019)

Creatine nanoliposome reverts the HPA-induced damage in complex II–III activity of the rats’ cerebral cortex - Nathana Jamille Mezzomo; Diego Becker Borin; Francine Ianiski; Barbara Dotto Fontana; Itiane Diehl de Franceschi; Juliane Bolzan; Renata Garcez; Mateus Grings; Belisa Parmeggiani; Liana da Silva Fernandes; Rodrigo de Almeida Vaucher; Guilhian Leipnitz; et al. (Molecular Biology Reports, 2019)

Glycerol monolaurate nanocapsules for biomedical applications: in vitro toxicological studies - Leonardo Quintana Soares Lopes; Pablo Sebastian Britto de Oliveira; Walter Paixão de Souza Filho; Rodrigo de Almeida Vaucher; Janice Luehring Giongo; Michele Rorato Sagrillo; Roberto Christ Vianna Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Grapevine virus L: a novel vitivirus in grapevine - Humberto Debat; Diego Zavallo; Reid Soltero Brisbane; Darko Vončina; Rodrigo P. P. Almeida; Arnaud G. Blouin; Maher Al Rwahnih; Sebastian Gomez-Talquenca; Sebastian Asurmendi (European Journal of Plant Pathology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Interaction with Pantoea agglomerans Modulates Growth and Melanization of Sporothrix brasiliensis and Sporothrix schenckii - Rodrigo Almeida-Paes; Fábio Brito-Santos; Manoel Marques Evangelista Oliveira; Alexandre Melo Bailão; Clayton Luiz Borges; Glauber Ribeiro de Souza Araújo; Susana Frases; Célia Maria de Almeida Soares; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2019)

Mild Paracoccidioidomycosis Misdiagnosed as a Subcutaneous Mycosis - Priscila Marques de Macedo; Dayvison Francis Saraiva Freitas; Leonardo Pereira Quintella; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes; Antonio Carlos Francesconi do Valle (Mycopathologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Renal effects of exendin-4 in an animal model of brain death - Natália Emerim Lemos; Cristine Dieter; Rodrigo Carlessi; Jakeline Rheinheimer; Letícia de Almeida Brondani; Cristiane Bauermann Leitão; Andrea Carla Bauer; Daisy Crispim (Molecular Biology Reports, 2019)

Increase of Candida antarctica lipase B production under PGK promoter in Pichia pastoris: effect of multicopies - Julia Macedo Robert; Maritza Ocampo Betancur; Antonio Carlos Oliveira Machado; Andrelisse Arruda; Viviane Castelo Branco Reis; Rodrigo Volcan Almeida; Fernando Araripe Gonçalves Torres; Pau Ferrer Alegre; Francisco Valero; Denise Maria Guimarães Freire (Brazilian Journal of Microbiology, 2019)

Mild Exercise Differently Affects Proteostasis and Oxidative Stress on Motor Areas During Neurodegeneration: A Comparative Study of Three Treadmill Running Protocols - Karla P. Melo; Carolliny M. Silva; Michael F. Almeida; Rodrigo S. Chaves; Tania Marcourakis; Sandra M. Cardoso; Marilene Demasi; Luis E. S. Netto; Merari F. R. Ferrari (Neurotoxicity Research, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Resilience thinking applied to fisheries management: perspectives for the mullet fishery in Southern-Southeastern Brazil - Michelle Alves de Abreu-Mota; Rodrigo Pereira Medeiros; Mauricio Almeida Noernberg (Regional Environmental Change, 2018)

Screening of some Croatian autochthonous grapevine varieties reveals a multitude of viruses, including novel ones - Darko Vončina; Rodrigo P. P. Almeida (Archives of Virology, 2018)

Generation mean analysis for nitrogen and phosphorus uptake, utilization, and translocation indexes at vegetative stage in tropical popcorn - Vinícius Costa Almeida; José Marcelo Soriano Viana; Leonardo Alves Risso; Cleberson Ribeiro; Rodrigo Oliveira DeLima (Euphytica, 2018)

Critical review of elementary flows in LCA data - Ashley Edelen; Wesley W. Ingwersen; Cristina Rodríguez; Rodrigo A. F. Alvarenga; Artur Ribeiro de Almeida; Gregor Wernet (The International Journal of Life Cycle Assessment, 2018)

Deltamethrin-induced nuclear erythrocyte alteration and damage to the gills and liver of Colossoma macropomum - Fernanda dos Santos Cunha; Natalino da Costa Sousa; Rudã Fernandes Brandão Santos; Juliana Oliveira Meneses; Márcia Valéria Silva do Couto; Fabrício Tavares Cunha de Almeida; José Guedes de Sena Filho; Paulo César Falanghe Carneiro; Alexandre Nizio Maria; Rodrigo Yudi Fujimoto (Environmental Science and Pollution Research, 2018)

Vermicompost dose and mycorrhization determine the efficiency of copper phytoremediation by Canavalia ensiformis - Natielo Almeida Santana; Caroline Maria Rabuscke; Valdemir Bittencourt Soares; Hilda Hildebrand Soriani; Fernando Teixeira Nicoloso; Rodrigo Josemar Seminoti Jacques (Environmental Science and Pollution Research, 2018)

Mercury speciation and Hg stable isotope ratios in sediments from Amazon floodplain lakes—Brazil - Beatriz Ferreira Araujo; Holger Hintelmann; Brian Dimock; Rodrigo de Lima Sobrinho; Marcelo Correa Bernardes; Marcelo Gomes de Almeida; Alex V. Krusche; Thiago Pessanha Rangel; Fabiano Thompson; Carlos Eduardo de Rezende (Limnology and Oceanography, 2018)
Hg concentrations and isotope ratios were measured to better characterize the mercury dynamics related to Hg cycling in Amazon floodplain lakes. We collected sediments, suspended particulate material (SPM), and plankton from floodplain lakes and compared then to sediments from rivers and soils of the central Amazon basin by measuring concentrations of total Hg (THg) and methylmercury (MMHg), and mercury isotope ratios. Concentrations of THg and MMHg in the lake sediments ranged to 69–109 ng g −1 and 0.62–4.78 ng g −1 , respectively. A positive correlation between THg and MMHg in soils and sediments suggest that inorganic Hg in this system is highly bioavailable and readily converted to MMHg. δ 202 Hg values ranged from −1.40‰ to −0.89‰ and Δ 199 Hg from −0.34‰ to −0.18‰. These values were comparable to those measured in riverine sediments (−2.14‰ to −1.23‰ and −0.51‰ to −0.05‰), suggesting a contribution of riverine sediments to lake sediments, at least during the season of rising waters, during which lake samples were collected. SPM on the other hand was much elevated in THg (590–1066 ng g −1 ) and showed more negative δ 202 Hg (−3.00 to −2.15), similar to those found in soils (−2.99‰ to −2.17‰), suggesting that Hg in SPM may originate from erosion of floodplain soils.

Tinea Capitis by Microsporum audouinii: Case Reports and Review of Published Global Literature 2000–2016 - Fábio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Anna Sales; Rodrigo Almeida-Paes (Mycopathologia, 2017)

Hepatic Disease with Portal Hypertension and Acute Juvenile Paracoccidioidomycosis: A Report of Two Cases and Literature Review - Priscila Marques de Macedo; Rodrigo Almeida-Paes; Dayvison Francis Saraiva Freitas; Fabio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; João Carlos de Almeida Soares; Andrea D’Ávila Freitas; Rosely Maria Zancopé-Oliveira; Antonio Carlos Francesconi do Valle (Mycopathologia, 2017)

Synthesis of a Goethite Pigment by Selective Precipitation of Iron from Acidic Coal Mine Drainage - Rodrigo de Almeida Silva; Jean Carlo Salomé dos Santos Menezes; Fabrício Abella Lopes; Ana Paula Kirchheim; Ivo Andre Homrich Schneider (Mine Water and the Environment, 2017)

Investigations into, and development of, a lyophilized and formulated recombinant human factor IX produced from CHO cells - Aline G. Almeida; Rodrigo C. V. Pinto; C. Mark Smales; Leda R. Castilho (Biotechnology Letters, 2017)

Inheritance of resistance to Meloidogyne enterolobii and individual selection in segregating populations of Psidium spp - Vicente Martins Gomes; Rodrigo Moreira Ribeiro; Alexandre Pio Viana; Ricardo Moreira de Souza; Eileen Azevedo Santos; Daniele Lima Rodrigues; Odimar Ferreira de Almeida (European Journal of Plant Pathology, 2017)

Deltamethrin as inductor agent of precocious ovarian degeneration in Rhipicephalus sanguineus s.l. (Acari: Ixodidae) ticks - Maria Izabel Camargo-Mathias; Natalia Rubio Claret Pereira; Camila da Silva Reis; Cristiane Regina de Almeida; Douglas Rodrigo dos Santos Mendes; Giselle Bezerra de Araújo; Lays Postali; Tober Figueroa; Allan Roberto Fernandes Ferreira; Juan Parente Santos; Patrícia Rosa de Oliveira (Experimental and Applied Acarology, 2017)

No evidence of transmission of grapevine leafroll-associated viruses by phylloxera (Daktulosphaira vitifoliae) - C. M. Wistrom; G. K. Blaisdell; L. R. Wunderlich; M. Botton; Rodrigo P. P. Almeida; K. M. Daane (European Journal of Plant Pathology, 2017)

Spittlebugs as vectors of Xylella fastidiosa in olive orchards in Italy - Daniele Cornara; Maria Saponari; Adam R. Zeilinger; Angelo de Stradis; Donato Boscia; Giuliana Loconsole; Domenico Bosco; Giovanni P. Martelli; Rodrigo P. P. Almeida; Francesco Porcelli (Journal of Pest Science, 2017)

Effects of dietary Gracilaria sp. and Alaria sp. supplementation on growth performance, metabolic rates and health in meagre (Argyrosomus regius) subjected to pathogen infection - Maria João Peixoto; Emílio Salas-Leitón; Francisca Brito; Luís Ferreira Pereira; Jon C. Svendsen; Teresa Baptista; Rui Pereira; Helena Abreu; Pedro Alexandre Reis; José Fernando Magalhães Gonçalves; Rodrigo Otávio de Almeida Ozório (Journal of Applied Phycology, 2017)

Tissue reaction of deproteinized bovine bone matrix grafting in ectopic site: histological study on sheep - João Ricardo Almeida Grossi; Rodrigo Bonacin; Viviane Rozeira Crivelaro; Allan Fernando Giovanini; João César Zielak; Tatiana Miranda Deliberador (Cell and Tissue Banking, 2016)

Copy number variations and genome-wide associations reveal putative genes and metabolic pathways involved with the feed conversion ratio in beef cattle - Miguel Henrique de Almeida Santana; Gerson Antônio Oliveira Junior; Aline Silva Mello Cesar; Mateus Castelani Freua; Rodrigo da Costa Gomes; Saulo da Luz e Silva; Paulo Roberto Leme; Heidge Fukumasu; Minos Esperândio Carvalho; Ricardo Vieira Ventura; Luiz Lehmann Coutinho; Haja N. Kadarmideen; et al. (Journal of Applied Genetics, 2016)

Paracoccidioides brasiliensis PS2: First Autochthonous Paracoccidioidomycosis Case Report in Rio de Janeiro, Brazil, and Literature Review - Priscila Marques de Macedo; Rodrigo Almeida-Paes; Mauro de Medeiros Muniz; Manoel Marques Evangelista Oliveira; Rosely Maria Zancopé-Oliveira; Regina Lana Braga Costa; Antonio Carlos Francesconi do Valle (Mycopathologia, 2016)

Behavioral profile assessment in offspring of Swiss mice treated during pregnancy and lactation with caffeine - Roberto Laureano-Melo; Anderson Luiz Bezerra da Silveira; Fernando de Azevedo Cruz Seara; Rodrigo Rodrigues da Conceição; Cláudio da Silva-Almeida; Bruno Guimarães Marinho; Fábio Fagundes da Rocha; Luís Carlos Reis; Wellington da Silva Côrtes (Metabolic Brain Disease, 2016)

Disease progression of vector-mediated Grapevine leafroll-associated virus 3 infection of mature plants under commercial vineyard conditions - G. Kai Blaisdell; Monica L. Cooper; Emily J. Kuhn; Katey A. Taylor; Kent M. Daane; Rodrigo P. P. Almeida (European Journal of Plant Pathology, 2016)

Interleukin-1 Receptor Antagonist Decreases Hypothalamic Oxidative Stress During Experimental Sepsis - Fazal Wahab; Nilton N. Santos-Junior; Rodrigo Pereira de Almeida Rodrigues; Luis Henrique A. Costa; Carlos Henrique R. Catalão; Maria Jose A. Rocha (Molecular Neurobiology, 2016)

Local hydrography and fishing drive life cycle strategies and population dynamics of the sea-bob shrimp Xiphopenaeus kroyeri in a coastal subtropical environment in Brazil - José Milton Andriguetto-Filho; Cláudio Dybas da Natividade; Frederico Pereira Brandini; Rodrigo de Almeida Teixeira (Hydrobiologia, 2016)

Plant trait distribution and the spatial reorganization of tree assemblages in a fragmented tropical forest landscape - Gabriel Mendes; Víctor Arroyo-Rodríguez; Wanessa Rejane Almeida; Severino Rodrigo Ribeiro Pinto; Valério D. Pillar; Marcelo Tabarelli (Plant Ecology, 2016)

Wood density, but not leaf hydraulic architecture, is associated with drought tolerance in clones of Coffea canephora - Paulo E. Menezes-Silva; Paulo C. Cavatte; Samuel C. V. Martins; Josimar V. Reis; Lucas F. Pereira; Rodrigo T. Ávila; Andréa L. Almeida; Marília C. Ventrella; Fábio M. DaMatta (Trees, 2015)

Microbial and sponge loops modify fish production in phase‐shifting coral reefs - Cynthia B. Silveira; Arthur W. Silva‐Lima; Ronaldo B. Francini‐Filho; Jomar S.M. Marques; Marcelo G. Almeida; Cristiane C. Thompson; Carlos E. Rezende; Rodolfo Paranhos; Rodrigo L. Moura; Paulo S. Salomon; Fabiano L. Thompson (Environmental Microbiology, 2015)
Summary Shifts from coral to algae dominance of corals reefs have been correlated to fish biomass loss and increased microbial metabolism. Here we investigated reef benthic and planktonic primary production, benthic dissolved organic carbon ( DOC ) release and bacterial growth efficiency in the A brolhos B ank, S outh A tlantic. Benthic DOC release rates are higher while water column bacterial growth efficiency is lower at impacted reefs. A trophic model based on the benthic and planktonic primary production was able to predict the observed relative fish biomass in healthy reefs. In contrast, in impacted reefs, the observed omnivorous fish biomass is higher, while that of the herbivorous/coralivorous fish is lower than predicted by the primary production‐based model. Incorporating recycling of benthic‐derived carbon in the model through microbial and sponge loops explains the difference and predicts the relative fish biomass in both reef types. Increased benthic carbon release rates and bacterial carbon metabolism, but decreased bacterial growth efficiency could lead to carbon losses through respiration and account for the uncoupling of benthic and fish production in phase‐shifting reefs. Carbon recycling by microbial and sponge loops seems to promote an increase of small‐bodied fish productivity in phase‐shifting coral reefs.

Physiological Changes Associated with Antioxidant Enzymes in Response to Sugarcane Tolerance to Water Deficit and Rehydration - Claudiana Moura dos Santos; Marcelo de Almeida Silva; Giuseppina Pace Pereira Lima; Fernanda Pacheco de Almeida Prado Bortolheiro; Marcela Cristina Brunelli; Lucas Almeida de Holanda; Rodrigo Oliver (Sugar Tech, 2015)

Uptake and allocation of nitrogen applied at low rates to soybean leaves - Clovis Pierozan; José Laércio Favarin; Rodrigo Estevam Munhoz de Almeida; Silas Maciel de Oliveira; Bruno Cocco Lago; Paulo Cesar Ocheuze Trivelin (Plant and Soil, 2015)

Surface water quality in the Sinos River basin, in Southern Brazil: tracking microbiological contamination and correlation with physicochemical parameters - Andréia Dalla Vecchia; Caroline Rigotto; Rodrigo Staggemeier; Mayra Cristina Soliman; Fernanda Gil de Souza; Andreia Henzel; Eliane Lemos Santos; Carlos Augusto do Nascimento; Daniela Muller de Quevedo; Juliane Deise Fleck; Larissa Schemes Heinzelmann; Sabrina Esteves de Matos Almeida; et al. (Environmental Science and Pollution Research, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Nitrogen metabolism in coffee plants in response to nitrogen supply by fertigation - Ana Paula Neto; José Laércio Favarin; André Rodrigues dos Reis; Tiago Tezotto; Rodrigo Estevam Munhoz de Almeida; José Lavres Junior; Luiz Antonio Gallo (Theoretical and Experimental Plant Physiology, 2015)

Toxicological effects of copper oxide nanoparticles on the growth rate, photosynthetic pigment content, and cell morphology of the duckweed Landoltia punctata - Cristina Moreira Lalau; Rodrigo de Almeida Mohedano; Éder C. Schmidt; Zenilda L. Bouzon; Luciane C. Ouriques; Rodrigo W. dos Santos; Cristina H. da Costa; Denice S. Vicentini; William Gerson Matias (Protoplasma, 2015)

Environmental and genetic effects on weight and visual score traits at postweaning in Suffolk sheep - Bárbara Mazetti Nascimento; Adriana Luiza Somavilla; Laila Talarico Dias; Rodrigo de Almeida Teixeira (Tropical Animal Health and Production, 2014)

Comparison of Commercial Methods and the CLSI Broth Microdilution to Determine the Antifungal Susceptibility of Candida parapsilosis Complex Bloodstream Isolates from Three Health Institutions in Rio de Janeiro, Brazil - Maria Helena G. Figueiredo-Carvalho; Leonardo S. Barbedo; Manoel M. E. Oliveira; Fábio Brito-Santos; Rodrigo Almeida-Paes; Rosely M. Zancopé-Oliveira (Mycopathologia, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Molecular tools reveal diets of insectivorous birds from predator fecal matter - Julie A. Jedlicka; Abhineet M. Sharma; Rodrigo P. P. Almeida (Conservation Genetics Resources, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Ixodid fauna and zoonotic agents in ticks from dogs: first report of Rickettsia rickettsii in Rhipicephalus sanguineus in the state of Mato Grosso do Sul, mid-western Brazil - Robson Ferreira Cavalcante de Almeida; Marcos Valério Garcia; Rodrigo Casquero Cunha; Jaqueline Matias; Elaine Araújo e Silva; Maria de Fatima Cepa Matos; Renato Andreotti (Experimental and Applied Acarology, 2013)

Cognitive Deficits in Machado–Joseph Disease Correlate with Hypoperfusion of Visual System Areas - Pedro Braga-Neto; Lívia Almeida Dutra; José Luiz Pedroso; André C. Felício; Helena Alessi; Ruth F. Santos-Galduroz; Paulo Henrique F. Bertolucci; Mário Luiz V. Castiglioni; Rodrigo Affonseca Bressan; Griselda Esther Jara de Garrido; Orlando Graziani Povoas Barsottini; Andrea Jackowski (The Cerebellum, 2012)

Phylogenetic signal and variation of visceral pigmentation in eight anuran families - Diogo B. Provete; Lilian Franco‐Belussi; Lia R. De Souza Santos; Rodrigo Zieri; Rafaela M. Moresco; Itamar A. Martins; Silvio C. De Almeida; Classius De Oliveira (Zoologica Scripta, 2012)
Provete, D. B, Franco‐Belussi, L., de Souza Santos, L. R., Zieri, R., Moresco, R. M., Martins, I. A., de Almeida, S. C., & de Oliveira, C. (2012). Phylogenetic signal and variation of visceral pigmentation in eight anuran families. — Zoologica Scripta , 41 , 547‐556. Visceral pigmentation is found in several organs and structures of ectothermic animals, comprising the extracutaneous pigmentary system. Its function is not well defined, although it is known that melanin is produced and stored inside pigmented cells. Previous studies demonstrated that the distribution of visceral pigmentation is neither homogeneous among organs among anuran species. We described the diversity of visceral pigmentation in 12 organs/structures from 32 anuran species belonging to eight families in a phylogenetic context. We also determined in which node(s) of the phylogeny there is more variation in the pigmentation and whether this variation has phylogenetic signal. The visceral pigment cells in organs and structures of the abdominal cavity varied among genera. All species had pigmentation in the urogenital and cardiorespiratory systems, whereas the stomach lacks pigmentation in all species. We also found a phylogenetic signal for pigmentation in all organs and structures taken together, besides heart, testes, lumbar parietal peritoneum and lumbar nerve plexus when considered separately. Overall, considering all organs, the highest diversity of categories of pigmentation was found in the nodes corresponding to Cruciabatrachia and Athesphatanura. This study constitutes the first step towards understanding the evolution of visceral pigmentation in anurans.

Phenotypic and Molecular Identification of Sporothrix Isolates from an Epidemic Area of Sporotrichosis in Brazil - Manoel Marques Evangelista Oliveira; Rodrigo Almeida-Paes; Mauro Medeiros Muniz; Maria Clara Gutierrez-Galhardo; Rosely Maria Zancope-Oliveira (Mycopathologia, 2011)

Density and Spatial Distribution of Buffy-tufted-ear Marmosets (Callithrix aurita) in a Continuous Atlantic Forest - Darren Norris; Fabiana Rocha-Mendes; Renato Marques; Rodrigo de Almeida Nobre; Mauro Galetti (International Journal of Primatology, 2011)

GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Rafael Y. Kuradomi; Márcio A. Figueiredo; Carlos F. C. Lanes; Carlos E. da Rosa; Daniela V. Almeida; Rodrigo Maggioni; Maeli D. P. Silva; Luis F. Marins (Transgenic Research, 2011)

Background matching behaviour and pathogen acquisition: plant site preference does not predict the bacterial acquisition efficiency of vectors - Arash Rashed; Nabil Killiny; Joyce Kwan; Rodrigo P. P. Almeida (Arthropod-Plant Interactions, 2011)

Comparative Study of 250 mg/day Terbinafine and 100 mg/day Itraconazole for the Treatment of Cutaneous Sporotrichosis - Glaucia Francesconi; Antonio Carlos Francesconi do Valle; Sonia Lambert Passos; Mônica Bastos de Lima Barros; Rodrigo de Almeida Paes; André Luiz Land Curi; José Liporage; Cássio Ferreira Porto; Maria Clara Gutierrez Galhardo (Mycopathologia, 2011)

Origin and Examination of a Leafhopper Facultative Endosymbiont - Patrick H. Degnan; Leonora S. Bittleston; Allison K. Hansen; Zakee L. Sabree; Nancy A. Moran; Rodrigo P. P. Almeida (Current Microbiology, 2011)

Treatment of experimental periodontal disease by a selective inhibitor of cyclooxygenase-2 with scaling and root planing (SRP) - Valdir Gouveia Garcia; Rodrigo Yuji Takano; Leandro Araújo Fernandes; Juliano Milanezi de Almeida; Leticia Helena Theodoro (Inflammopharmacology, 2010)

Strain-specific alfalfa water stress induced by Xylella fastidiosa - Matthew P. Daugherty; Joao R. S. Lopes; Rodrigo P. P. Almeida (European Journal of Plant Pathology, 2010)

Sporotrichosis Caused By Sporothrix globosa in Rio De Janeiro, Brazil: Case Report - Manoel Marques Evangelista de Oliveira; Rodrigo de Almeida-Paes; Mauro de Medeiros Muniz; Monica Bastos de Lima Barros; Maria Clara Gutierrez Galhardo; Rosely Maria Zancope-Oliveira (Mycopathologia, 2010)

Effect of low-level laser therapy (GaAs 904 nm) in skeletal muscle fatigue and biochemical markers of muscle damage in rats - Ernesto Cesar Pinto Leal Junior; Rodrigo Álvaro Brandão Lopes-Martins; Patrícia de Almeida; Luciano Ramos; Vegard V. Iversen; Jan Magnus Bjordal (European Journal of Applied Physiology, 2010)

Heart failure increases atrogin-1 and MuRF1 gene expression in skeletal muscle with fiber type-specific atrophy - Robson Francisco Carvalho; Eduardo Paulino Castan; Cesar Augusto Coelho; Francis Silva Lopes; Fernanda Losi Alves Almeida; Aline Michelin; Rodrigo Wagner Alves de Souza; João Pessoa Araújo; Antonio Carlos Cicogna; Maeli Dal Pai-Silva (Journal of Molecular Histology, 2010)

Phylogenetic Placement of Pentatomid Stink Bug Gut Symbionts - Simone S. Prado; Rodrigo P. P. Almeida (Current Microbiology, 2009)

Spread of an introduced vector‐borne banana virus in Hawaii - RODRIGO P.P. ALMEIDA; GORDON M. BENNETT; MANDY D. ANHALT; CHI‐WEI TSAI; PATRICK O’GRADY (Molecular Ecology, 2009)
Emerging diseases are increasing in incidence; therefore, understanding how pathogens are introduced into new regions and cause epidemics is of importance for the development of strategies that may hinder their spread. We used molecular data to study how a vector‐borne banana virus, Banana bunchy top virus (BBTV), spread in Hawaii after it was first detected in 1989. Our analyses suggest that BBTV was introduced once into Hawaii, on the island of Oahu. All other islands were infected with isolates originating from Oahu, suggesting that movement of contaminated plant material was the main driving factor responsible for interisland spread of BBTV. The rate of mutation inferred by the phylogenetic analysis (1.4 × 10 −4 bp/year) was similar to that obtained in an experimental evolution study under greenhouse conditions (3.9 × 10 −4 bp/year). We used these values to estimate the number of infections occurring under field conditions per year. Our results suggest that strict and enforced regulations limiting the movement of banana plant material among Hawaiian islands could have reduced interisland spread of this pathogen.

Guarana (Paullinia cupana var. sorbilis), an anciently consumed stimulant from the Amazon rain forest: the seeded-fruit transcriptome - Paula C. S. Ângelo; Carlos G. Nunes-Silva; Marcelo M. Brígido; Juliana S. N. Azevedo; Enedina N. Assunção; Alexandra R. B. Sousa; Fernando J. B. Patrício; Mailson M. Rego; Jean C. C. Peixoto; Waldesse P. Oliveira; Danival V. Freitas; Elionor R. P. Almeida; et al. (Plant Cell Reports, 2008)

Epidemiological and Clinical Aspects of the First Outbreak of Bovine Mastitis Caused by Prototheca zopfii in Goiás State, Brazil - Válter Ferreira Félix Bueno; Albenones José de Mesquita; Rodrigo Balduino Soares Neves; Marcos Almeida de Souza; Andréa Rentz Ribeiro; Edmar Soares Nicolau; Antônio Nonato de Oliveira (Mycopathologia, 2006)

Xylella fastidiosa Cultivation on a Minimal Solid Defined Medium - Rodrigo P. P. Almeida; Renee Mann; Alexander H. Purcell (Current Microbiology, 2004)

Detection and Characterization of Membrane Microheterogeneity by Resonance Energy Transfer - Luís M. S. Loura; Rodrigo F. M. de Almeida; Manuel Prieto (Journal of Fluorescence, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)